Assessment of nanofiltration efficiency for simultaneous concentration of copper and recovery of acid from highly acidic wastewater - Bencheng Hu; Haowen Wu; Wenhao Su; Keyu Yao; Li Long; Pengfei Sun; Yongcheng Wang; Lin Lin; Hao Guo; Xiao-yan Li (Water Research, 2026)

Turbulence-induced detachment of fine particles from bubble surfaces and associated flow field characteristics - Hailing He; Zhixin Sun; Xiaoheng Li; Xiaokang Yan; Lijun Wang; Haijun Zhang; Li Lin; Jincai Ran (Minerals Engineering, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Exploratory analysis of HLA SNPs associated with occult HBV infection: a multicenter case–control study in Chinese blood donors - Lin Zhou; Ying Yan; Huimin Ji; Huizhen Sun; Zhuoqun Lu; Le Chang; Lunan Wang (Human Genetics, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Sustainable photothermal superhydrophobic coatings based on magnetically recyclable MOF-derived carbon for efficient anti/de-icing - Jiaxing Zhang; Peijian Sun; Weijie Lin; Yipeng Wang; Xin Cui; Mengyue Wang; Xuehui Sun; Peipei Zhang; Bin Yan (Chemical Engineering Journal, 2026)

pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Inhibition of Sonic Hedgehog signaling pathway by GANT61 alleviates adenomyosis by suppressing epithelial-to-mesenchymal transition, cell migration and proliferation - Zaifan Lin; Simiao Yan; Qingzhen Ran; Qianxin Yang; Haixin Lin; Jingtong Sun; Yi Chen; Xiuchi Zhong; Yingzhou Tian; Wanqun Chen (Tissue and Cell, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

Comprehensive quality profiling and comparative metabolic characterization of seven dominant fresh-eating Chinese olive (Canarium album Lour.) cultivars in Southern China - Lijuan Fu; Wenjing Liu; Yuying Xu; Xiangxin Lin; Jia Guo; Hao Chen; Jianwei Fu; Sun'an Yan (Food Chemistry, 2026)

Multi-omics analyses reveal BPA accelerates glioma progression via cell cycle dysregulation - Shimin Lin; Yan Wei; Yuze Wang; Guidong Zhu; Diange Zhang; Feihu Zhao; Chi Zhang; Chengwei Wang; Zhongzheng Sun (Environmental Pollution, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Cascade delivery and synergistic ferroptosis-apoptosis induction via hybrid-membrane-coated MOF nanoparticles for glioblastoma therapy - Yue Huang; Zesheng Sun; Guiping Jiang; Qianqian Liu; Jialiang Lin; Song Deng; Yan Song; Yu Yang; Yinhao Chen; Yi Wang; Rongqin Huang; Jinlong Shi (Chemical Engineering Journal, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Assimilatory sulfate reduction potential in the plastisphere microbiome is linked to plastic mineralization in sulfur-rich mining-impacted river sediments - Tianle Kong; Zhili Du; Jianhua Zhou; Zhihao Zheng; Jian Zhang; Shui Zhang; Feng Jiang; Xiaoxu Sun; Wei Huang; Ruijian Zhang; Fangbai Li; Wenjie Lin; et al. (Water Research, 2026)

CFD–DEM simulation of seabed scour around submarine pipelines with particle-scale analysis of sediment transport - Dong Wang; Dong Li; Jianguo Lin; Sheng Yan; Kun Zheng; Jiawen Sun (Ocean Engineering, 2026)

The response of Beauveria bassiana to zinc exposure in controlling Hyphantria cunea: Short-term efficiency improvement and long-term efficiency reduction - Guotong Sun; Lin Zheng; Mingtao Tan; Shanchun Yan; Dun Jiang (Journal of Hazardous Materials, 2026)

Selective reduction of hazardous volatiles from baijiu using spent grain-derived activated carbon: Flavor preservation and DFT-elucidated adsorption mechanisms - Ziyang Wu; Yunran Shen; Yahan Yan; Yaqi Teng; Jie Lin; Huan Cheng; Hehe Li; Jinyuan Sun; Xingqian Ye; Mingquan Huang; Baoguo Sun (Food Chemistry, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Experimental and numerical research on ultimate bearing capacity of steel-concrete-steel composite deep beams with UHPC/ECC considering interfacial bonding - Youzhu Lin; Yazhe Zou; Ming Sun; Jiachuan Yan (Engineering Structures, 2026)

Toxic effects of acute atrazine exposure on the physiological functions and transcriptional levels in non-targeted marine invertebrates (Chlamys nobilis) - Jing Sun; Beiyu Yan; Yaoting Liu; Qing Lin; Weili Wang; Hongkuan Zhang; Huaiping Zheng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Built-in electric field-driven d-band engineering in metal sulfide heterojunctions for high-efficiency electro-Fenton degradation of antibiotics - Xiangwei Zou; Yue Wang; Xinyu Wang; Lin Lin; Xiao-yan Li; Chitou Lei; Xiaojun Fan; Weng Ian Ieong; Qinfen Gu; Lianpeng Sun; Chao Yang (Chemical Engineering Journal, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Tailored electronic structure of copper species in spatially controlled Cu-SSZ-13 for efficient denitration - Pengkai Jin; Wang Song; Qianni Cheng; Wanting Yan; Gehui Wang; Jingfang Sun; Changjin Tang; Lin Dong (Chemical Engineering Journal, 2026)

Observational evidence of stronger subsidence and more active photochemistry aloft associated with severe ozone pollution over rural areas - Zhuang Wang; Yujia Chen; Hao Zhang; Xianguang Ji; Xiaoyun Sun; Meng Zhang; Xinfeng Lin; Shaowei Yan; Congzi Xia; Kaidi Zhang; Xintong Chen; Yizhi Zhu; et al. (Atmospheric Research, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Nonlinear coupled dynamic response of TLP wind turbine with redundant mooring under complex environmental loads and multi-tendon failures - Mingyang Wei; Jianhua Zhang; Ke Sun; Yian Chen; Zaibin Lin; Yan Geng; Hongwen Liu; Yanghua Ou (Ocean Engineering, 2026)

Strain-Dominated Pathways of Floating Marine Debris in Xiamen Bay Identified Using Lagrangian Coherent Structures - Haowei Sun; Wenxin Lin; Xiao-Hai Yan; Jianwei Lin; Zishen Li; Lijing Gao; Yuwu Jiang; Xin Zhang (Ocean Modelling, 2026)

Spatiotemporal differences in traffic efficiency and CO2 emissions across day types: A city-level data-driven analysis of cooperative vehicle-infrastructure systems - Bin Sun; Haoyu Xu; Zhaolang Wu; Qijun Zhang; Lin Wu; Yan Liu; Yanan Mi; Hongjun Mao (Journal of Environmental Management, 2026)

Genomic insights into high GABA production by Levilactobacillus brevis Q3–11 and its application in developing functional kiwifruit juice - Bingrui Guo; Qi Wu; Xu Yan; Wei Ji; Shufeng Yin; Sufang Zhang; Yiwei Dai; Xiangyu Sun; Tingting Ma; Xinping Lin (International Journal of Food Microbiology, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Gelation properties and swallowing characteristics of chia seed gum/fish gelatin composite gels as dysphagia management - Peng-Yuan Sun; Lin Li; Bin Lai; Ce Wang; Jia-Nan Yan; Qian Zhang; Hai-Tao Wu (Food Chemistry, 2026)

Contrasting impacts of policy interventions and population mobility on organic aerosols and oxygenated volatile organic compounds in Beijing - Yu Zhang; Weiqi Xu; Wei Zhou; Jintai Lin; Mengying Wang; Yan Li; Siqi Zeng; Ziyi Zhang; Xiaomin Cheng; Yang Yang; Yele Sun (Environmental Pollution, 2026)

Laser-assisted growth of ligand-free nanocrystals for grain-boundary passivation and suppression of non-radiative defects in lead-free Cs3Sb2I9 solar cells - Wenbin Lin; Yuhua Jin; Cai Yan; Ke Sun; Yu Cao; Aumber Abbas; Ali Hassan (Chemical Engineering Journal, 2026)

Phenolic constituents from Potentilla kleiniana and their chemotaxonomic significance - Yuhuan Sun; Xunqin Yin; Zhaoyang Lin; Shumeng Guo; Yangyang Song; Yan Li; Huankai Yao (Biochemical Systematics and Ecology, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Role of NADPH oxidase generated O2− in seed germination and cold stress response of Brassica napus - Wei-liang Qi; Guo-yan Bao; Mei-ying Sun; Wen-juan Ma; Xuan-ting Yang; Xiang-hong Gao; Miao-xin Zhou; Qi-lin Wang (Protoplasma, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Construction of a process-driven 3D spatio-temporal model for precision soil remediation: Coupling dynamic retention with multi-objective cost optimization - Zhengda Lin; Bingjie Yan; Xinhao Sun; Caoqingqing Li; Liyan Liu; Dan Zhong; Jun Zhang (Process Safety and Environmental Protection, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

Effect of impeller design and operating conditions on food waste hydrolysis: Insights from experiments and computational fluid dynamics simulations - Yahui Miao; Di Wu; Siqi Wang; Muhammad Ahmar Siddiqui; Huaimin Wang; Guneet Kaur; Sophie L.K.W. Roelants; Chi Yan Tso; Zheng Sun; Carol Sze Ki Lin (Bioresource Technology, 2026)

Coactive adaptation to combined drought and UV-B stress in highland barley (qingke) through hormonal and nutrient crosstalk - Noman Shoaib; Liling Liu; Nishbah Mughal; Xiaoyun Bai; Fakhar Zaman; Yan Pan; Juan Zhang; Junjie Pan; Xiaogang Wu; Xiaoming Sun; Lin Zhang; Kaiwen Pan (Plant and Soil, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Titanium white waste acid for efficient iron removal from gypsum: A study on leaching kinetics and a sustainable "utilizing waste to treat waste" strategy - Yan Lin; Hongjuan Sun; Qian Zhao; Lei Jiang; Tongjianng Peng (Journal of Environmental Chemical Engineering, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Carrier-free immobilization of α-galactosidase using novel cross-linkers: Robust inclusion body-derived CLEAs for efficient hydrolysis of raffinose family oligosaccharides in soymilk - Tong Sun; Wenyue Sun; Shutong Lin; Yan Liu; Lili Lu (Food Chemistry, 2026)

Dietary myricetin inhibits AGEs formation during thermal processing in different pattern diets and alleviates AGEs-induced intestinal epithelial damage in Caco-2 cells - Luyan Liu; Kaiyue Sun; Xin Xie; Yanghui Chen; Jiahui Wang; Yaxin He; Junjie Yu; Meng Huang; Yan Lin; Juan Chen; Jian Liu; Xian Zhang (Food Chemistry, 2026)

Citral-loaded PVA-PVP hydrogel pad: Preparation, physicochemical properties, characterization, and application for blueberry preservation - Haifeng Rong; Wenna Li; Yuxuan Li; Sixu Lin; Runan Zhao; Yufeng Xu; Bingxin Sun; Yunhe Zhang; Xuerui Yan (Food Packaging and Shelf Life, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

A cyclic ecological strategy for ameliorating saline-alkali soils using biochar and Cenchrus fungigraminus (JUJUNCAO) - Shaojuan Yan; Lingyi Hu; Jian Ma; Lihuai Ma; Dongmei Lin; Hongying Sun (Environmental Research, 2026)

Controlled in situ semi-conversion strategy for fabricating a “embedded-covering type” FeCo-LDH/Ag/MIL-88B Z-scheme heterojunction: efficient meloxicam removal via adsorption-photodegradation and enhanced antibacterial activity - Xinru Lin; Di Sun; Zonghe Yu; Junyang Zhang; Peng Yan; Yang Wang; Yuzhong Gao (Desalination, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Chemical constituents from the rhizomes of Abelmoschus manihot (L.) and their chemotaxonomic significance - Ruiqing Wu; Yuhuan Sun; Shaoshan Gao; Shumeng Guo; Zhaoyang Lin; Changjiang Ying; Yan Li (Biochemical Systematics and Ecology, 2026)

The synergy of active and passive satellite sensors for robust sea-fog detection: A two-stage machine-learning model with constraints from ICOADS - Luyu Yan; Xuehua Fan; Disong Fu; Hongrong Shi; Lin Chen; Bo Li; Zhuhui Jiang; Xiaoqiong Zhen; Xiaoguang Sun; Xiangao Xia (Atmospheric Research, 2026)

Overexpression of TkMYC2 enhances drought tolerance and rubber-producing capacity in transgenic Taraxacum kok-saghyz - Changping Zhang; Fengqi Luo; Xiaodong Li; Zihan Guo; Jialong Sun; Yixuan Lin; Gaoquan Dong; Jie Yan (Planta, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Electrochemically assisted surface oxidation/activation for ultrathin layered Hv-NiCoCu-OOH @NiCoCu-LDH and research on enhanced energy storage characteristics - Chunxiao Shi; Lin Sun; Fangrong Yan; Yunchao Wu; Weijing Liu; Yu Liu; Qingjun Yang; Guiquan Liu; Runmei Luo; Weidong Shi (Chemical Engineering Journal, 2026)

Vernalization-responsive intronless genes in faba bean and the development of KASP markers - Xiaocen Liu; Jinyang Liu; Jiali Huang; Shuoqian Zhao; Shengqi Chen; Yun Lin; Qiang Yan; Jingbin Chen; Chenchen Xue; Ranran Wu; Yonghai Sun; Yuhua He; et al. (Plant Cell Reports, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

A new insight into PCDD/Fs degradation from MSWI fly ash during CaCO3 oligomer crystallization via low-temperature thermal induction - Yizhe Shen; Jie Chen; Dianwei Sun; Ruilin Zhu; Jie Liu; Haijun Wang; Hong Yu; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Waste Management, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Seeing structure, sensing softening: Decoding the microstructural mediation between optical properties and peach firmness using spatial frequency domain imaging - Yuan Gao; Hanfeng Yan; Zhizhong Sun; Yan Lin; Dong Hu; Lijuan Xie; Yibin Ying (Food Research International, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

Green flocculant of Aspergillus niger fungus cultured from food waste hydrolysate for enhanced sludge dewatering - Yingfei Sun; Yijiao Chang; Yuxuan Wang; Zuohong Chen; Zhu Liang; Jiao Chen; Bing Li; Yongcheng Wang; Xiao-yan Li; Lin Lin (Bioresource Technology, 2026)

Acquisition and temporal transcriptomic characteristics of cambial meristematic cells in Camptotheca acuminata under in vitro culture conditions - Yundan Xiong; Shuang Yu; Jiale Sun; Zhiyu Chen; Fanfan Lin; Yifan Cai; Tianping Huang; Xin Yin; Yan Zheng; Yunqiang Yang; Xiangxiang Kong; Yongping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Comparing the performance of different hyperspectral satellite imaging spectroscopy in mapping methane point-source emissions - Fei Li; Keer Lin; Yingqi Yan; Shengxi Bai; Qidan Huang; Chenxi Feng; Shiwei Sun; Shaohua Zhao; Wei Zhou; Chunyan Zhou; Jun Lin; Xinwei Zhang; et al. (Remote Sensing of Environment, 2026)

Three-dimensional numerical investigation of vortex-induced motion of low aspect ratio cylinders - Jin Miao; Hongyuan Sun; Haihua Lin; Dexin Liu; Shuo Ren; Kefeng Yan; Jing Xu (Ocean Engineering, 2026)

Multi-dimensional dynamic trust routing for multi-attack underwater acoustic sensor networks - Lin Sun; Xiaohong Shen; Yifan Yuan; Weiliang Xie; Yongsheng Yan; Haiyan Wang (Ocean Engineering, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Fixel-based analysis to detect early fiber-specific white matter alterations in sporadic patients with amyotrophic lateral sclerosis - Mingjie Ma; Qingguo Ren; Xiaohan Sun; Pengfei Lin; Wei Li; Yuying Zhao; Xiangshui Meng; Chuanzhu Yan; Shuangwu Liu (Brain Imaging and Behavior, 2026)

Enhanced performance of pulse-powered electrokinetic remediation for Cd/Pb-contaminated soil by iron-carbon reactive barriers - Peihong Zheng; Zongping Cai; Xiufen Yu; Pingfang Yan; Ronglian Lin; Yu Huang; Zhaoyu Leng; Shuiyu Sun (Process Safety and Environmental Protection, 2026)

Enhanced and sustainable extraction of acetic acid from wastewater using a novel ternary deep eutectic solvent - Yan Zhou; Yue Zhao; Lin Su; Kangjia Sun; Jianguang Qi; Yinglong Wang; Yufeng Hu (Journal of Cleaner Production, 2026)

Maternal prenatal mercury exposure from rice and its association with newborn neurobehavioral development - Chunfang Gan; Xinbin Feng; Kun-Lin Yang; Guangyi Sun; Weijun Luo; Qiang Yang; Wenjin Zhang; Yan Shi; Li Wang; Min Xiong; Mahmoud A. Abdelhafiz (Environmental Pollution, 2026)

Peak load prediction and interface behavior analysis of steel–ECC composite slabs: Experiments, simulations and theoretical models - Youzhu Lin; Haijun Wang; Ming Sun; Yuanbo Hu; Di Yao; Jiachuan Yan (Engineering Structures, 2026)

Magic chain-flip triboelectric nanogenerator for multi-mode wind and raindrop energy harvesting - Mingxia Chen; Jiahong Yang; Rui Gu; Hai Yan; Zhenghao Li; Siqi Sun; Nuo Xu; Ziwei Huo; Zhong Lin Wang; Qijun Sun; Xiangde Lin (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Dynamics of sulfate reduction regulate arsenic mobilization and speciation in paddy soils in response to root exudates - Guo-Hao Zhang; Hong-Yan Wang; Jun-Jie Lin; Guo-Xin Sun; Zheng Chen; Zhi-Guo Yu (Plant and Soil, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Oncogenic and immunological roles of LAMP5 across cancers and its potential utility in bladder cancer - Zhenni Lin; Kun Zhao; Sijia Wang; Jianting Liu; Yijie Liu; Kemeng Qiang; Mingzhi Huang; Ning Sun; Peipei Zhang; Yan Hu; Yongyong Lu; Honglei Jin (Apoptosis, 2026)

Stabilizing photogranule systems under low-light and limited-aeration: From operational strategy to underlying mechanism - Xiaojing Yang; Lan Tang; Jinke Sun; Fahui Ji; Peng Qi; Meng Yan; Yanjuan Luo; Chen Yang; Yanting Lin; Hui Lu (Water Research, 2026)

Microinterface effects of catalytic materials on PMS/PDS-mediated degradation of organic pollutants: Mechanistic insights, structural influences, and enhancement strategies - Yifan Chen; Jingyi Sun; Bingjie Yan; Yihe Wang; Zhengda Lin; Wei Zuo; Yu Tian; Jun Zhang (Water Research, 2026)

Sustainable production of high-purity crystalline FePO4 from sludge for battery electrodes - Xuan Wang; Yijiao Chang; Zhu Liang; Anjie Li; Yiru Wu; Bohua Wen; Bing Li; Feiyun Sun; Xiao-yan Li; Bruce E. Logan; Lin Lin (Water Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

An improved ISPH model for simulating wave–current interactions and turbulence evolution over submerged reefs - Dong Wang; Haopeng Wang; Sheng Yan; Jianguo Lin; Jiawen Sun; Jingdan Cui; Junyi Xi; Tao Liu (Ocean Engineering, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

From genes to products: High-efficiency biosynthesis and holistic optimization strategies for monounsaturated fatty acids - Lu-Wei Xu; Yan-Cheng Lin; Yi-Ting Shen; Xin Qi; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Microbiology, 2026)

Nanoformulated resveratrol enhanced the treatment of atherosclerosis - Cai Cheng; Yan Lin; Xin Chen; Yang Xie; Xing Jiang; Jinting Chen; Yanling Wu; Zaiyi Luo; Jiayi Xu; Zhirong Zhang; Changguang Wang; Pei Jing; et al. (Chemical Engineering Journal, 2026)

Enhanced fermentation for lactic acid production from food waste via hydrothermal pretreatment: performance evaluation and metagenomic analysis - Zuohong Chen; Jiayu Zhang; Lin Lin; Yingfei Sun; Xiao-yan Li; Bing Li (Bioresource Technology, 2026)

Lactobacillus johnsonii JJB3 Ameliorates Oxidative Stress-Induced Intestinal Injury and Mitochondrial Damage by Promoting BNIP3L-Mediated Mitophagy - Xingmei Liu; Jinge Xin; Ning Sun; Yuhua Qin; Haonan Huang; Benhao Chen; Lixiao Duan; Yanxi Zhou; Dandan Wang; Bo Jing; Yan Zeng; Dong Zeng; et al. (Probiotics and Antimicrobial Proteins, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A physically-refined regional climate model for the Tibetan Plateau - Kun Yang; Xu Zhou; Xiaogang Ma; Deliang Chen; Fahu Chen; Yongjiu Dai; Yaozhi Jiang; Anning Huang; Yanluan Lin; Jiarui Liu; Hui Lu; Jing Sun; et al. (Science Bulletin, 2025)

Exogenous proanthocyanidins improved postharvest quality and resistance to Botrytis cinerea infection of strawberry via enhanced non-enzymatic antioxidants accumulation and salicylic acid signaling pathway - Yuanxiu Lin; Ziqing Sun; Xiao Wang; Shuaipeng Cao; Yin Liu; Shuangyang Liu; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Yan Wang; Wen He; et al. (Postharvest Biology and Technology, 2025)

Experimental study and theoretical analysis on ultimate bearing capacity of steel-concrete-steel deep beams with UHPC after freeze-thaw cycles - Youzhu Lin; Chuanbo Yu; Ming Sun; Xinya Mao; Pengxi Jia; Jiachuan Yan (Engineering Structures, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Catechol-engineered manganese ferrite nanozyme with superior antioxidant activity promotes diabetic wound healing - Wenhui Wang; Leyu Zhang; Lin Yang; Xinsheng Li; Yan Xiao; Baocheng Chang; Yan Zhao; Ruxia Liu; Shao-Kai Sun (Chemical Engineering Journal, 2025)

Micellar co-delivery of ibuprofen and zonisamide selectively to inflamed tissue following spinal cord injury - Shuzao Wang; Yan Lin; Zhenzhen He; Zaiyi Luo; Yanling Wu; Yan Wang; Xing Jiang; Jinting Chen; Jili Wu; Xingyue Zhong; Zhirong Zhang; Changguang Wang; et al. (Chemical Engineering Journal, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Correction to: Cisternal Contrast‑Enhanced MRI Reveals Post‑Stroke Glymphatic Impairment and Compensatory Metabolic Waste Clearance via Microglia/Macrophages - Chengfeng Sun; Chanchan Li; Luyi Lin; Lekang Yin; Jiaojiao Li; Yan Ren; Weijun Tang; Yanmei Yang (Translational Stroke Research, 2025)

Cisternal Contrast-Enhanced MRI Reveals Post-Stroke Glymphatic Impairment and Compensatory Metabolic Waste Clearance via Microglia/Macrophages - Chengfeng Sun; Chanchan Li; Luyi Lin; Lekang Yin; Jiaojiao Li; Yan Ren; Weijun Tang; Yanmei Yang (Translational Stroke Research, 2025)

Associations Between Dietary Habits, Oral Microbiota, and Dental Caries in Adolescents - Haiyan Yue; Pei Shen; Qiumin Huang; Shuchun Lin; Jie Shen; Yetong Wang; Zhonghan Sun; Xinhe Qi; Yuzhou Jiang; Changzheng Yuan; Duohong Zou; Yan Zheng; et al. (Phenomics, 2025)

Transcription factor E93 regulates vitellogenesis via the vitelline membrane protein 26Ab gene in Chilo Suppressalis - Siyang Chen; Yingjuan Sun; Suijie Kuang; Yan Tang; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Hongshuai Gao; Youzhi Li; Lin Qiu (Molecular Biology Reports, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Facile synthesis of high loading and highly electron-delocalized Co single-atom catalyst for PMS activation: An in-depth study of molecular orbital and catalytic mechanisms - Mu Li; Dongsheng Xia; Wei Zhang; Feiyun Sun; Guan Zhang; Lin Lin; Zhengjun Gong; Bing Li; Xiao-yan Li (Journal of Hazardous Materials, 2025)

Lignosulfonate provides a sustainable strategy for soil acidification mitigation through dual suppression of nitrification-driven protons and active aluminum - Mao Gao; Yan Yang; Zhuoran Teng; Yuchen Shu; Huijuan Duan; Feixiang Li; Chengliang Sun; Xianyong Lin (Journal of Cleaner Production, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Revealing the characteristic honey-like aroma formation in honey-scented black tea via molecular sensory analysis - Peng Zhang; Weiwei Wu; Bangxing Ma; Changkun Zheng; Qi Lin; Xinyi Zhao; Yan Huang; Fuming Lin; Weijiang Sun (Food Chemistry, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Ultimate strength of bamboo scrimber-concrete composite beams with UHPC and ECC: Experimental investigation, finite element simulation and prediction model - Mengqi Cao; Youzhu Lin; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Activation of peroxymonosulfate by magnesium−modified biochar for the degradation of imidacloprid: Effectiveness and mechanisms - Xianguo Ji; Hao Lin; Yan Zhang; Jianbo Lu; Yanxiang Zhang; Hongwei Sun; Gang Wang; Xiaoyong Yang; Wei Li; Jinming Duan; Yucan Liu (Chemical Engineering Journal, 2025)

Monocyte/macrophage-mediated transport and intratumoral bacteria-responsive ZIF nanoplatform for enhanced immunotherapy against microsatellite-stable colorectal cancer - Xietao Ye; Yeyang Sun; Lin Yang; Chen Chen; Shihao Li; Shuo Dong; Xiaoying Qin; Xiaoqi Li; Congyan Liu; Jiege Huo; Yuping Liu; Yan Chen (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

First total ozone column observations from the Ozone Monitoring Suite-Nadir (OMS-N) onboard China’s FengYun-3F satellite - Jian Xu; Yapeng Wang; Lin Chen; Dmitry Efremenko; Lanlan Rao; Gegen Tana; Shuanghui Liu; Qian Wang; Jinghua Mao; Yongmei Wang; Ling Sun; Huanhuan Yan; et al. (Science China Earth Sciences, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

Bio-driven Fe bond restructuring in bio-iron systems enhances electron transfer for chain elongation - Quan Liao; Lianpeng Sun; Huanzhong Deng; Siru Zhou; Mingxuan Li; Xinzhe Zhu; Chao Yang; Xiao-yan Li; Lin Lin; Ruo-hong Li (Water Research, 2025)

KHDC3 affects the lineage differentiation of early embryo by regulating the differential distribution of YAP signal - Qian Xu; Yuling Lin; Lina Yu; Yang Zhang; Na Kong; Guijun Yan; Haixiang Sun; Guangyi Cao (Theriogenology, 2025)

Optimization of water intake systems: Based on water-carbon relationships and sustainable development goals - Shixiong Du; Huaiwei Sun; Baowei Yan; Changmei Liang; Siyue Li; Yuanyao Ye; Ming Ye; Lin Chen; Wenxin Zhang (Journal of Hydrology, 2025)

One-step baking soda activation induces N, S-self-doped Ginkgo biloba-derived carbon for efficient chlorine removal - Jiaxi Wang; Limei Sun; Shuaishuai Zhang; Yao Zhang; Ran Zhang; Lin Tian; Yan Xu; Ming Song; Wenchang Zhuang; Wenyi Tan (Journal of Environmental Chemical Engineering, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Numerical Analysis of Thermal–Structural Coupling for Subsea Dual-Channel Connector - Feihong Yun; Yuming Du; Dong Liu; Xiaofei Wu; Minggang Tang; Qiuying Yan; Peng Gao; Yu Chen; Xu Zhai; Hanyu Sun; Songlin Zhang; Shuqi Lin; et al. (Journal of Marine Science and Engineering, 2025)
In deep-sea oil and gas development scenarios, deep-sea dual-channel connectors often face the risk of seal failure due to internal and external temperature difference loads. To address this issue, this paper systematically establishes equivalent heat transfer models for the key parts of the connector based on the third-type boundary condition. On this basis, the quantitative correlation between the equivalent thermal conductivity, composite heat transfer coefficient and temperature of each part is explored. Using the finite element numerical simulation method, the transient temperature field of the connector under three working conditions (heating, cooling and temperature shock) is simulated and analyzed, revealing the temperature distribution characteristics and temperature change trends of the maximum temperature difference of each key component of the connector; combined with thermal–structural coupling simulation, the temperature field is converted into static load, to determine the behavior of the contact stress on the sealing surface under different temperature–pressure coupling working conditions; in addition, by placing the test prototype in a high-low temperature cycle chamber, the seal performance tests under pressurized and non-pressurized working conditions are carried out to verify the reliable sealing performance of the connector under variable temperature conditions. The results of this paper provide comprehensive theoretical support and an experimental basis for the thermodynamic optimization design of deep-sea connectors and the improvement of the reliability of the sealing system.

Analysis of spontaneous failure of lithium-ion battery under micromechanical deformation - Chuang Qi; Hongtao Yan; Hao Cheng; Yuemeng Zhang; Chunjing Lin; Siqi Chen; Xi Liu; Li Lao; Yazhou Sun; Qiang Wang (Process Safety and Environmental Protection, 2025)

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

River inflow and seawater intrusion shape distinct phytoplankton communities in jinghai bay, a coastal bay of the Yellow Sea - Jinchang Sui; Dongsheng Ding; Yan Zhang; Lin Zhu; Zhengguo Cui; Jun Sun; Yuqiu Wei (Marine Environmental Research, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Hydrogel pads loaded with essential oil contribute to maintaining blueberry quality after transportation - Yuxuan Li; Haifeng Rong; Sixu Lin; Yaohui Zheng; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Food Packaging and Shelf Life, 2025)

Interleukin-6-taregeted dual-drug nanoparticles enhance glioblastoma chemotherapy by facilitating blood-brain barrier penetration and alleviating cardiotoxicity - Zesheng Sun; Jialiang Lin; Yue Huang; Qianqian Liu; Xucheng Zhu; Yu Yang; Ya Wen; Chunbin Shao; Weiquan Liao; Yan Song; Sharon Prince; Yi Wang; et al. (Chemical Engineering Journal, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Red mud amendments reduce cadmium mobility in paddy soil and limit cadmium accumulation in rice grains: A mechanistic investigation - Jiali Yan; Xuwei Li; Jintao Li; Jiankang Zhou; Jiamin Shi; Kangfu Liu; Xin Chen; Shiqi Zhou; Weiwei Sun; Fuqing Sui; Xiaochen Lin; Lei Zhang; et al. (Plant and Soil, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Anecic earthworm enhanced the soil multifunctionality by affecting soil bacterial abundant taxa - Yan Hu; Bing-Jie Jin; Xin-Yuan Li; Qing-Lin Chen; Cheng-Liang Sun; Gang Li; Xian-Yong Lin (Soil Ecology Letters, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Discovery of 7-azaindole-3-acrylamide inhibitors of inflammasomes/IL-1β for the treatment of inflammatory bowel disease - Yuyun Yan; Xiuxiu Zhang; Ruiwen Wu; Xiangting Liang; Yiming Luo; Jie Yang; Dan Wu; Geng Lin; Ping Sun; Zhongjin Yang; Wenhui Hu (Molecular Diversity, 2025)

Remote sensing assessment of urban vegetation's dust retention for mitigating atmospheric particulate pollution - Wei Yang; Yan Yu; Wenpeng Lin; Jia Song; Yue Sun; Yuxun Zhang; Wei Zhang; Yue Li (Urban Climate, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Organ-specific lithium accumulation and its toxic effects on female reproduction - Qigang Fan; Yi Sun; Qingjun Shen; Yuxin Wang; Jisheng Nie; Yanbing Lin; Shuaishuai Xing; Yan Li; Benhong Xu; Jianjun Liu; Xiaoting Shen; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Ambient PM2.5 exposure, physical activity, and cardiovascular dysfunction: Analysis of CHARLS data and experimental study in mice - Hao Chang; Kun Pan; Xi Zhang; Zhonghua Lu; Yihui Wang; Di Liu; Yafen Lin; Yan Wu; Yi Lin; Qingyu Huang; Junchao Duan; Zhiwei Sun; et al. (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Extending CO2 and CH4 footprints of created habitats through drainage ditches in a subtropical coastal region of southeastern China - Yan Zhang; Yule Lin; Ping Yang; Hong Yang; Guanpeng Chen; Wenjing Liu; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenbo Lin; Kam W. Tang (Environmental Research, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Polymersomal vincristine-PLK1 inhibitor boosts immunogenic cell death and antitumor immunity - Yan Zhao; Li Cao; Songsong Zhao; Zhenzhen Zhai; Xueling Tang; Lin Chen; Huanli Sun; Zhiyuan Zhong (Chemical Engineering Journal, 2025)

Changes in soil organic carbon and its forms in recovering alpine meadows of various lengths in relation to altitude - Chunying Lin; Xilai Li; Huafang Sun; Xiaoxue Su; Hongmei Li; Rongna Liu; Chengyi Li; Yonghui Hou; Shizhen Zhu; Di Yu; Liyan Zhang; Jiexia Li; et al. (CATENA, 2025)

A new phenylpropanoid glycoside from the aerial parts of Saposhnikovia divaricata (Turcz.) Schischk. and its chemotaxonomic significance - Zhenqiang Liu; Yan Pan; Yan Sun; Yuxuan Lin; Shuang Liu; Qian Zhang; Juan Pan; Wei Guan; Haixue Kuang; Anam Naseem; Yan Liu; Bingyou Yang (Biochemical Systematics and Ecology, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Mitochondrial dysfunction and aging: multidimensional mechanisms and therapeutic strategies - Pei Wei; Xiaoyan Zhang; Chi Yan; Siyu Sun; Zhigang Chen; Fei Lin (Biogerontology, 2025)

Description of Chrysonotomyia ophelimi sp. nov., Parasitoid of the Eucalyptus Gall Wasp Ophelimus bipolaris in China (Hymenoptera: Eulophidae) - Yuan-Hao Li; Jing-Hui Su; Jin Hu; Jin-Bo Sun; Yan Qin; Zoya Yefremova; Xia-Lin Zheng (Neotropical Entomology, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Ignition, combustion and pollutant emissions characteristics of excavated waste in low oxygen concentration and O2/CO2 atmosphere - Jingwen Lv; Beibei Yan; Shengquan Zhou; Zhaoting Wu; Xiaoyun Liu; Sensen Lu; Xiaochao Zhu; Yunan Sun; Jian Li; Fawei Lin; Guanyi Chen (Waste Management, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

Polyhalogenated heterocycle additive induced in-situ 3D gelatinous polymerization with polysulfides for shuttle effect inhibited lithium-sulfur batteries - Xingkai Ma; Xinmei Song; Yaoda Wang; Junchuan Liang; Tianyu Shen; Zuoao Wu; Lina Qin; Huan Li; Tianchen Yu; Huaizhu Wang; Zuoxiu Tie; Yichao Yan; et al. (Chemical Engineering Journal, 2025)

Crack regulating by multi-level sensory structure towards personalized heath monitoring, human motion tracking, and robotic arm control - Huinan Wang; Huijuan Lin; Zhiyuan Zhang; Ke Chen; Yan Yan; Naidi Yang; Kun Rui; Jingwen Sun; Jixin Zhu (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Variations in optimal seismic intensity measures for shallowly buried bias loess tunnels - Weiyu Sun; Juncen Lin; Bo Wang; Songhong Yan (Journal of Mountain Science, 2025)

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

Shale wastewater treatment policies recommended by integrated knowledge graph and probability-based algorithms - Li He; Yugeng Luo; Mengxi He; Tong Sun; Yiming Yan; Wei Ye; Yupeng Lin (Environmental Monitoring and Assessment, 2025)

Decipher syntrophies and adaptive response towards enhancing conversion of propionate to methane under psychrophilic condition - Miao Yan; Zhijian Shi; Xinjie Zhang; Xiaofeng Lin; Yongming Sun; Xingyu Cheng; Hailin Tian; Ying Li (Water Research, 2025)

Rapid electrothermal upcycling hexachlorobutadiene (HCBD) polluted distillation residue into turbostratic graphene for enhanced electromagnetic wave absorption - Tong Chen; Yunxiao Zhao; Hanyang Sun; Xinyu Niu; Pei Li; Yan Xia; Xiaoqing Lin; Xiaodong Li; Ying Wang; Jianhua Yan; Chen Sun (Journal of Hazardous Materials, 2025)

Process optimization and mechanism for removal of chlorine from ultrasonic-enhanced Municipal Solid Waste Incineration fly ash water washing - Shunda Lin; Lijuan Sun; Zeinab Khalid; Guojun Lv; Xuguang Jiang; Jianhua Yan (Journal of Environmental Chemical Engineering, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Development of a Mixotrophic Strategy for Efficient Cultivation of a Coccolithophore, Chrysotila roscoffensis - Luyao Zhang; Zhichao He; Yan Sun; Jian Li; Pengfei Cheng; Nicolas Spiros Agathos; Chengxu Zhou; Lin Zhang; Jichang Han (Journal of Ocean University of China, 2025)

Bronze alloying recipes of Yue state: new evidence from bronze artifacts and metal ingots unearthed at the Dahutou site in Shaoxing, Zhejiang, China - Linxiang Liu; Xiaolei You; Xiansheng Yan; Junling Lin; Zhenfei Sun; Xiaotong Wu (Archaeological and Anthropological Sciences, 2025)

Loss of KIFC1 activity induces spindle instability and actin defects during porcine oocyte maturation - Yu-Ran Wang; Peng-Jie Wang; Le-Yan Tao; Lin-Lin Hu; Qiang-Qiang Liu; Shao-Chen Sun; Jing-Xi Wei; Yue Wang (Theriogenology, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Improving thermal comfort and cognitive ability of manual workers by cooling garment of different temperatures based on EEG analysis - Haiying Wang; Renjie Yan; Huxiang Lin; Junli Sun; Hang Meng; Rongfu Hou; Yongwang Hao; Songtao Hu; Jun Zhang (Energy and Buildings, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Glioma stem cell membrane-camouflaged photothermal nanozyme for synergistic antitumor via dual-targeted drug delivery across blood-brain barrier - Jialiang Lin; Zesheng Sun; Yue Huang; Qianqian Liu; Mujie Shen; Chunbin Shao; Weiquan Liao; Yu Yang; Yan Song; Yi Wang; Rongqin Huang; Jinlong Shi (Chemical Engineering Journal, 2025)

Synthesis and antibacterial activity of environmentally friendly sulfonium compounds - Jing Li; Wenyang Chen; Xinrui Bi; Yue Lin; Chengcai Liu; Yan Sun; Guinan Shen (Medicinal Chemistry Research, 2025)

Arsenic and its associated metabolism genes in Chinese soils: a comprehensive investigation of mine and paddy soils - Yu-Ting Lin; Rui-Lian Yu; Gong-Ren Hu; Jing-Wei Sun; Yu Yan (Journal of Soils and Sediments, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Identification of intermediate-silicic cumulates in the Emeishan large igneous province, SW China - Kwan-Nang Pang; Yang Sun; Christina Yan Wang; Sun-Lin Chung; Hao-Yang Lee (Lithos, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

Discovering potential fumigants against Tribolium castaneum from essential oils using GC-MS and chemometric approaches - Yan Yan Lin; Min Xing Zhang; Miao Sun; Lu Sheng Wan; You Zhou; Jing Sheng Chen (Journal of Stored Products Research, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Study on a ventilating vest with thermoelectric cooling to improve thermal comfort and cognitive ability - Haiying Wang; Guangyan Zhang; Huxiang Lin; Junli Sun; Rengjie Yan; Hang Meng; Songtao Hu; Hui Zhu (Energy and Buildings, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

A single-atom manganese nanozyme mediated membrane reactor for water decontamination - Jiahao Sun; Minjia Yan; Guangdong Tao; Runbin Su; Xuanming Xiao; Qiangshun Wu; Feng Chen; Xi-Lin Wu; Hongjun Lin (Water Research, 2025)

Utilization of drinking water treatment sludge with coal fly ash to make permeable bricks for low impact development - Pu Li; Feiyun Sun; Ye Dong; Lei Wen; Lin Lin; Xiao-yan LI (Resources, Conservation and Recycling, 2025)

Novel insights into halogenated carbazoles (HCZs) prediction in tap water: A comparative study of grey relational analysis-based neural networks - Qianfeng He; Wanting Xu; Guolong Chen; Zhen Wang; Yan Liang; Hongjie Sun; Huachang Hong; Hongjun Lin; Zeqiong Xu (Journal of Cleaner Production, 2025)

Deciphering the distinct roles of polyketide synthase subunits in polyunsaturated fatty acid and lipid accumulation in Schizochytrium sp. - Hong-Xuan Wu; Wen-Qian Yang; Zi-Xu Zhang; Yan-Cheng Lin; Wang Ma; Xiao-Man Sun; He Huang (Food Bioscience, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Anterior and posterior cerebral white matter show different patterns of microstructural alterations in young adult smokers - Lei Jiang; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2024)

miR-24-3p inhibits lipid synthesis and progesterone secretion in chicken granulosa cells via ERK1/2 signaling pathway - Yanrong Gong; Zhongzhen Lin; Hao Sun; Chunlin Yu; Mohan Qiu; Xia Xiong; Lingqian Yin; Donghao Zhang; Yan Wang; Chaowu Yang; Yiping Liu (Theriogenology, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Greenhouse gas concentrations and diffusive fluxes in the middle reach of the Lancang River before and after damming - Xudong Zhou; Xingcheng Yan; Qiuwen Chen; Jianyun Zhang; Hao Sun; Hanlu Yan; Yuchen Chen; Yuqing Lin (Journal of Hydrology, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Carbon dots-based stimuli-responsive hydrogel for in-situ detection of thiram on fruits and vegetables - Hongxia Li; Yanan Hu; Zhen Lin; Xu Yan; Chunyan Sun; Dong Yao (Food Chemistry, 2024)

Effects of Limosilactobacillus reuteri on ruminal microbiota, muscle protein metabolism, and flavor of Sunit lamb - Ting Liu; Maoqin Zhai; Taiwu Zhang; Min Zhang; Chenlei Wang; Yanni Zhang; Yan Duan; Lin Su; Ye Jin; Lina Sun (Food Bioscience, 2024)

Nature-inspired temperature-adaptive module: Achieving all-season passive thermal regulation for buildings - Lin Liang; Jianheng Chen; Kaixin Lin; Xueming Yang; Sai Liu; Chui Ting Kwok; Hao Pan; Ziai Liu; Aiqiang Pan; Siru Chen; Yihao Zhu; Wei Li; et al. (Energy and Buildings, 2024)

Experimental study on improving effect of cooling garment on thermal comfort and salivary IgA concentration - Huxiang Lin; Haiying Wang; Renjie Yan; Junli Sun; Hang Meng; Songtao Hu (Energy and Buildings, 2024)

Platelet-hitchhiking biomimetic nanoplatforms pry precisely tumor seed and growing soil for inhibiting tumor recurrence and metastasis - Yan Zhang; Weiting Sun; Guozheng Xing; Dunwan Zhu; Lin Mei; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Application of an α-galactosidase from Bacteroides fragilis on structural analysis of raffinose family oligosaccharides - Heyang Zu; Xuecui Yan; Jing Wu; Jingying Zhao; Kevin H. Mayo; Yifa Zhou; Liangnan Cui; Hairong Cheng; Lin Sun (Carbohydrate Polymers, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Function-Genes and Disease-Genes Prediction Based on Network Embedding and One-Class Classification - Weiyu Shi; Yan Zhang; Yeqing Sun; Zhengkui Lin (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Effects of salinity and temperature on growth performance, biochemical composition, and biosilification process of Cyclotella cryptica - Yicun Zhao; Yan Sun; Zhengfeng Zhu; Yuhang Li; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Albiflorin Alleviates Severe Acute Pancreatitis-Associated Liver Injury by Inactivating P38MAPK/NF-κB Signaling Pathway - Haitao Li; Xiangpeng Zeng; Dongjie Sun; Xingfeng Qi; Dazhou Li; Wen Wang; Yan Lin (Biochemical Genetics, 2024)

Sensitivity Assessment on Satellite Remote Sensing Estimates of Primary Productivity in Shelf Seas - Xiaolong Zhao; Jianan Sun; Qingjun Fu; Xiao Yan; Lei Lin (Journal of Marine Science and Engineering, 2024)
The vertically generalized production model (VGPM) is one of the most important methods for estimating marine net primary productivity (PP) using remote sensing. However, different data sources and parameterization schemes of the input variables for the VGPM can introduce uncertainties to the model results. This study compared the PP results from different data sources and parameterization schemes of three major input variables (i.e., chlorophyll-a concentration (Copt), euphotic depth (Zeu), and maximum photosynthetic rate (PoptB)) and evaluated the sensitivity of VGPM in the Yellow and Bohai Seas on the inputs. The results showed that the sensitivity in the annual mean PP was approximately 40%. Seasonally, the sensitivity was lowest in the spring (35%), highest in the winter (70%), and approximately 60% in the summer and autumn. Spatially, the sensitivity in nearshore water (water depth

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Corrigendum to ‘Machine-learning-based corrections of CMIP6 historical surface ozone in China during 1950–2014’ [Environ. Pollut. 357 (2024) 124397] - Yuanxi Tong; Yingying Yan; Jintai Lin; Shaofei Kong; Zhixuan Tong; Yifei Zhu; Yukun Yan; Zhan Sun (Environmental Pollution, 2024)

HZSM-5 supported with N-doped Fe for microwave catalytic pyrolysis of lignin - Yan Wang; Kangqi Cao; Wenlong Sun; Xiangxi Lin; Jianwei Wang; Jessica Villarreal; Longzhi Li (Chemical Engineering Journal, 2024)

An unsaturated chain carbonate additive contributing to high-performance LiFePO4//graphite battery at broad temperature range - Xin-Lin Zhang; Bin Dong; Yi Jin; Jia-Shun Song; Li Li; Jia-Yu Wang; Yu-Ying Zhu; Yan-Yun Sun (Chemical Engineering Journal, 2024)

Novel ternary deep eutectic solvents pretreatment of corn stalk to realize high-value utilization - Zhiwen Jia; Xinlong Li; Shibo Xu; Yan Sun; Lin Chen; Jiamin Ye; Wanyu Li; Tao Wu; Junyu Li; Shiyang Wang; Xiwei Xu (Chemical Engineering Journal, 2024)

Development of Ce-doped NH2-UiO-66(Zr) photocatalysts for efficient CO2 reduction in an aqueous system - Chao Yu; Xianjin Zhang; Chenxu Song; Yanna Wang; Jing Lin; Zhonglu Guo; Yujie Zhang; Zhenya Liu; Chunsheng Li; Yan Sun; Chengchun Tang; Yang Huang (Chemical Engineering Journal, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Exosomal miR-21-5p derived from endometrial stromal cells promotes angiogenesis by targeting TIMP3 in ovarian endometrial cysts - Liyuan Sun; Yan Cheng; Jing Wang; Di Wu; Lin Yuan; Xiaoyu Wei; Yan Li; Jie Gao; Guangmei Zhang (Journal of Molecular Medicine, 2024)

Iron driven organic carbon capture, pretreatment, recovery and upgrade in wastewater: Process technologies, mechanisms, and implications - Quan Liao; Lianpeng Sun; Hui Lu; Xianglin Qin; Junhong Liu; Xinzhe Zhu; Xiao-yan Li; Lin Lin; Ruo-hong Li (Water Research, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Complete chromium removal via photocatalytic reduction and adsorption using bimetallic UiO-66(Zr/Al) - Chao Yu; Chenxu Song; Xianjin Zhang; Yanna Wang; Jing Lin; Yang Huang; Zhonglu Guo; Chunsheng Li; Yujie Zhang; Zhenya Liu; Chengchun Tang; Yan Sun (Journal of Environmental Chemical Engineering, 2024)

Characterization of volatile compounds and identification of key aroma compounds in different aroma types of Rougui Wuyi rock tea - Yilin Liang; Zhihui Wang; Lingzhi Zhang; Haomin Dai; Weiwei Wu; Zhiqiang Zheng; Fuming Lin; Jie Xu; Yan Huang; Weijiang Sun (Food Chemistry, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Rheological Behavior and Microstructures in the Hybrid Gel of Scallop ( Patinopecten yessoensis ) Male Gonad Hydrolysates Modified by κ-Carrageenan and Methyl-β-Cyclodextrin - Wen Sun; Xiao-Fan Cui; Jia-Nan Yan; Xin-Yu Jiang; Lin Li; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2024)

DUSP8-attenuated ERK1/2 signaling mediates lipogenesis and steroidogenesis in chicken granulosa cells - Hao Sun; Zhongzhen Lin; Yanrong Gong; Lingqian Yin; Donghao Zhang; Yan Wang; Yiping Liu (Theriogenology, 2024)

Comparative study of atmospheric brown carbon at Shanghai and the East China Sea: Molecular characterization and optical properties - Dongmei Cai; Chunlin Li; Jingxin Lin; Wenwen Sun; Miaomiao Zhang; Tao Wang; Munila Abudumutailifu; Yan Lyu; Xiaojuan Huang; Xiang Li; Jianmin Chen (Science of The Total Environment, 2024)

The mechanism of using magnetized-ionized water in combination with organic fertilizer to enhance soil health and cotton yield - Shudong Lin; Quanjiu Wang; Mingjiang Deng; Kai Wei; Yan Sun; Wanghai Tao (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Thermal runaway and gas production characteristics of semi-solid electrolyte and liquid electrolyte lithium-Ion batteries: A comparative study - Chunjing Lin; Hongtao Yan; Chuang Qi; Zhenyan Liu; Dinghong Liu; Xi Liu; Li Lao; Zhaoyang Li; Yazhou Sun (Process Safety and Environmental Protection, 2024)

AlphaFold-guided redesign of a plant pectin methylesterase inhibitor for broad-spectrum disease resistance - Yeqiang Xia; Guangzheng Sun; Junhua Xiao; Xinyi He; Haibin Jiang; Zhichao Zhang; Qi Zhang; Kainan Li; Sicong Zhang; Xuechao Shi; Zhaoyun Wang; Lin Liu; et al. (Molecular Plant, 2024)

Glutathione‑iron hybrid nanozyme-based colorimetric sensor for specific and stable detection of thiram pesticide on fruit juices - Xu Yan; Ruiqi Zou; Qiqi Lin; Yuan Ma; Aixin Li; Xun Sun; Geyu Lu; Hongxia Li (Food Chemistry, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Machine-learning-based corrections of CMIP6 historical surface ozone in China during 1950–2014 - Yuanxi Tong; Yingying Yan; Jintai Lin; Shaofei Kong; Zhixuan Tong; Yifei Zhu; Yukun Yan; Zhan Sun (Environmental Pollution, 2024)

An optically responsive cancer vaccine for inducing robust anti-tumor immunity by apoptotic body carrying nanoadjuvants - Limin Jin; Shupei Sheng; Yan Zhang; Weiting Sun; Lin Mei; Dunwan Zhu; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Redistribution and activation of inert N-configuration in metallic electron donor towards boosted oxygen reaction kinetics for zinc-air batteries - Yiyao Cao; Yakai Chen; Ke Chen; Lingling Sun; Wenhao Si; Yan Yan; Huijuan Lin; Jixin Zhu; Peilei He; Yan Lu; Haijiao Xie; Kun Rui (Chemical Engineering Journal, 2024)

High-performance static formation of methane hydrate in fixed bed constructed by incorporating expanded graphite into polyimide foam - Xinran Sun; Daiming Liu; Zhibing Xuan; Yongtao Zhang; Guodong Zhang; Chen Chen; Mengting Sun; Yan Lin; Jie Zhong; Fei Wang (Chemical Engineering Journal, 2024)

A novel player of methylotrophic methanogensis pathway in boosting anaerobic digestion of corn stover with effluents recycling - Lianhua Li; Fan Lin; Yan He; Quanlin Zhao; Yao Yubo; Yongming Sun; Wen Luo; Haiwei Ren; Ying Guo (Chemical Engineering Journal, 2024)

Mutual-benefit modification of the coagulant solution and fly ash for enhanced sludge dewatering - Yingfei Sun; Yuexing Wang; Jianjun Zhang; Chengzhi Zhu; Zuohong Chen; Zehui Yu; Bing Li; Ruo-hong Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

Experimental study on improving effect of cooling garment on thermal comfort and EEGs - Huxiang Lin; Haiying Wang; Renjie Yan; Junli Sun; Hang Meng; Songtao Hu; Yihang Ji (Building and Environment, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Taurine prevented the decline of fillet quality and muscle antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) fed non-fishmeal diet - Shun-Shi Sun; Liang-Chao Yan; Lin Feng; Wei-Dan Jiang; Yang Liu; Ling Tang; Pei Wu; Xiao-Qiu Zhou (Aquaculture, 2024)

Preparation and identification of galacto-mannooligosaccharides generated from guar gum by a recombinant β-mannanase from Bacteroides fragilis (BF0736) - Xiang Wang; Xuecui Yan; Yaoqi Liu; Zhicong Song; Kevin H. Mayo; Lin Sun; Liangnan Cui; Yifa Zhou (Food Hydrocolloids, 2024)

Strength design of built-up radially battened columns subject to axial compression and arbitrary directional bending moment - Hao-Jun Sun; Yan-Lin Guo (Engineering Structures, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Physics-informed neural network simulation of two-phase flow in heterogeneous and fractured porous media - Xia Yan; Jingqi Lin; Sheng Wang; Zhao Zhang; Piyang Liu; Shuyu Sun; Jun Yao; Kai Zhang (Advances in Water Resources, 2024)

Node Load and Location-Based Clustering Protocol for Underwater Acoustic Sensor Networks - Haodi Mei; Haiyan Wang; Xiaohong Shen; Zhe Jiang; Yongsheng Yan; Lin Sun; Weiliang Xie (Journal of Marine Science and Engineering, 2024)
Clustering protocols for underwater acoustic sensor networks (UASNs) have gained widespread attention due to their importance in reducing network complexity. Congestion occurs when the intra-cluster load is greater than the upper limit of the intra-cluster information transmission capacity, which leads to a dramatic deterioration of network performance despite the reduction of network complexity. To avoid congestion, we propose a node load and location-based clustering protocol for UASNs (LLCP). First, a node load and location-based optimization mechanism is proposed. The number of cluster members is optimized based on node load and location to maximize the number of cluster members while avoiding congestion. Then, a node degree and location-based cluster member selection mechanism is proposed to select the optimal cluster members. Finally, a priority-based clustering mechanism is proposed. The node clustering order is adjusted based on the clustering priority to maximize the reduction of network complexity by increasing the average number of cluster members. Simulation results show that our proposed LLCP minimizes the network complexity while avoiding congestion.

A novel approach for sludge deep-dewatering via flowing-out enhancement but not relying on cell lysis and bound water release - Hao Zhang; Wen-Hui Liu; Yun-Yan Gao; Ping Sun; Yuan-Ping Zeng; Lin-Lin Ma; Jiang-Nan Wu; Shun-Gui Zhou; Xi-Qin Cui; Raymond Jianxiong Zeng; Hou-Feng Wang (Water Research, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Spatiotemporal distributions of dissolved N2O concentration, diffusive N2O flux and relevant functional genes along a coastal creek in southeastern China - Ping Yang; Yongxin Lin; Hong Yang; Chuan Tong; Linhai Zhang; Derrick Y.F. Lai; Dongyao Sun; Lishan Tan; Lele Tang; Yan Hong; Kam W. Tang (Journal of Hydrology, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Ultrasound-responsive metal–organic framework-based nanosystem for sonodynamic therapy/amplified ferroptosis/IDO-blockade osteosarcoma immunotherapy - Qingjian Lei; Wei Zhou; Shijie Gao; Ningxiang Sun; Bo Wang; Haixia Yang; Jie Wang; Yu Zhao; Qing Chen; Jian Tian; Lin Cai; Feifei Yan (Chemical Engineering Journal, 2024)

Kidney Function and Cardiovascular Disease: Evidence from Observational Studies and Mendelian Randomization Analyses - Wenjun Yang; Xuemei Wu; Manying Zhao; Jianying Hu; Chenhao Lin; Zhendong Mei; Jing Chen; Xu-jie Zhou; Sheng Nie; Jing Nie; Xiang Gao; Yan Zheng; et al. (Phenomics, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Discrete recoil control system modelling and optimal recoil damping of deepwater drilling riser systems - Bao-Lin Zhang; Yue-Ting Sun; Yan-Dong Zhao; Qing-Long Han; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Manure replacing synthetic fertilizer improves crop yield sustainability and reduces carbon footprint under winter wheat–summer maize cropping system - Jincan Niu; Qudsia Saeed; Wenning Wang; Runze Zhang; Lin Liu; Fenglian Lv; Jiaxing Xu; Yan Han; Panxin Zhang; Changlu Hu; Hu Xu; Benhua Sun; et al. (Journal of Environmental Management, 2024)

Optical investigation on effects of diesel injection strategy on ammonia/diesel dual fuel combustion characteristics and flame development - Wenpeng Zeng; Wanchen Sun; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Separation and reutilization of heavy metal ions in wastewater assisted by p-BN adsorbent - Jianzheng Zhen; Lingshan Miao; Zhilong Lin; Jiahao Sun; Haoxiang Yan; Yunzhan Ying; Zenglong Wu; Wenkai Song; Weiyang Lv; Changsheng Song; Yuyuan Yao (Chemosphere, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

PM2.5-induced premature senescence in HUVECs through the SIRT1/PGC-1α/SIRT3 pathway - Qing Yan; Rao Zheng; Yi Li; Juan Hu; Meidi Gong; Manman Lin; Xuecong Xu; Jing Wu; Shikun Sun (Science of The Total Environment, 2024)

Microplastics and cadmium affect invasion success by altering complementarity and selection effects in native community - Feng He; Jianfan Sun; Justin S.H. Wan; Mohsin Nawaz; Qaiser Javed; Linxuan Pan; Wajid Ali Khattak; Yanwen Bo; Yan Xiang; Guangqian Ren; Xin Lin; Daolin Du (Science of The Total Environment, 2024)

Enhancing pakchoi (Brassica chinensis L.) agriculture with magnetized-ionized brackish water and organic fertilizers: A sustainable approach to soil quality and crop yield optimization - Shudong Lin; Quanjiu Wang; Kai Wei; Yan Sun; Fanfan Shao; Qingyuan Lei; Mingjiang Deng (Journal of Cleaner Production, 2024)

Experimental evaluation and theoretical modeling of eco-friendly bamboo scrimber-UHPC members with enhanced shear connectors - Youzhu Lin; Chen Wang; Ming Sun; Jiachuan Yan (Journal of Cleaner Production, 2024)

Degradation of atrazine by N-doped graphitic carbon encapsulated Nickel-iron alloy via heterogeneous activation of peroxymonosulfate - Xiuping Sun; Hao Lin; Yucan Liu; Yan Zhang (Journal of Environmental Chemical Engineering, 2024)

Temperature sensitivity of soil-borne fungal phytopathogens depends on niche breadth and land use types - Bangguo Yan; Yi Sun; Guangxiong He; Xuemei Wang; Lin Li; Xuewen Yue; Liangtao Shi; Haidong Fang (Fungal Ecology, 2024)

Comparative analysis of indoor thermal environment characteristics and occupants’ adaptability: Insights from ASHRAE RP-884 and the Chinese thermal comfort database - Liu Yang; Feixiang Wang; Shengkai Zhao; Siru Gao; Haiyan Yan; Zhen Sun; Zhiwei Lian; Lin Duanmu; Yufeng Zhang; Xiang Zhou; Bin Cao; Zhaojun Wang; et al. (Energy and Buildings, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Efficient removal and transformation of Cr(VI) from alkaline wastewater to form a ferrochromium spinel multiphase via a modified ferrite process - Yingying Lan; Yiwei Sun; Shasha Chu; Bo Yang; Lijuan Zhang; Lin Xiao; Jinlin Li; Xiaochao Yuan; Xin Yan; Vladimir V. Galvita; Xintai Su (Chemosphere, 2024)

Effects of urbanization and topography on thermal comfort during a heat wave event: A case study of Fuzhou, China - Zefeng Zheng; Xinlu Lin; Li Chen; Chao Yan; Ting Sun (Sustainable Cities and Society, 2024)

Environmentally realistic dose of tire-derived metabolite 6PPD-Q exposure causes intestinal jejunum and ileum damage in mice via cannabinoid receptor-activated inflammation - Yan Yang; Nan Sun; Jia Lv; Haojia Chen; Hongqian Wang; Jingjing Xu; Jiayue Hu; Lin Tao; Mingliang Fang; Yichao Huang (Science of The Total Environment, 2024)

4,5-Difluoro-1,3-dioxolan-2-one as a film-forming additive improves the cycling and thermal stability of SiO/C anode Li-ion batteries - Yong-Qi Wang; Lin-Jie Xie; Hui-Qi Sun; Xiang Wang; Hai-Lin Zhou; Yan Tang; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Population pharmacokinetic/pharmacodynamic modeling of nifekalant injection with varies dosing plan in Chinese volunteers: a randomized, blind, placebo-controlled study - Juanjuan Jiang; Li Xu; Lin Chai; Li Zhang; Hong Liu; Yan Yan; Xiaoyuan Guan; Hui Sun; Lei Tian (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Effects of dietary glutamine supplementation on growth performance, intestinal digestive ability, antioxidant status and hepatic lipid accumulation in Xenocypris davidi (Bleeker,1871) - Yuehan Wang; Zuxiang Peng; Lin Yan; Xin Gao; Lin Wu; Shuchang Cui; Mengyuan Zhou; Tongjun Ren; Wei Wang; Shuhao Sun; Yuzhe Han; Hang Sun (Aquaculture International, 2024)

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Exogenous stimulation-induced biosynthesis of volatile compounds: Aroma formation of oolong tea at postharvest stage - Lin Zeng; Shan Jin; Yan-Qun Xu; Daniel Granato; Yan-Qing Fu; Wei-Jiang Sun; Jun-Feng Yin; Yong-Quan Xu (Critical Reviews in Food Science and Nutrition, 2024)

Shared micromobility as a first- and last-mile transit solution? Spatiotemporal insights from a novel dataset - Zehui Yin; Greg Rybarczyk; Anran Zheng; Lin Su; Bingrong Sun; Xiang Yan (Journal of Transport Geography, 2024)

Towards efficient and accurate CO2 sequestration optimization: Integrating hierarchical spatio-temporal information into deep-learning-based surrogate models - Jingqi Lin; Kai Zhang; Liming Zhang; Piyang Liu; Wenfeng Peng; Huaqing Zhang; Xia Yan; Chen Liu; Yongfei Yang; Hai Sun; Jun Yao (Fuel, 2024)

Optical diagnostic study of internal and external EGR combined with oxygenated fuels of n-butanol, PODE3 and DMC to optimize the combustion process of FT synthetic diesel - Wanchen Sun; Genan Zhu; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Wenpeng Zeng; Xin Zhang; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Cyclic tests and shear resistance design of stiffened corrugated steel plate shear walls - Chen-Bao Wen; Hao-Jun Sun; Ya-Zhou Liu; Yan-Guo Hou; Jia-Qi Zuo; Yan-Lin Guo (Engineering Structures, 2024)

AM fungi reduce grass–legume competition by increasing nutrient access - Jiqiong Zhou; Jinchao Gong; Shan Liu; Adam B. Cobb; Gaowen Yang; Xiangjun Li; Feida Sun; Yan Peng; Yanhong Yan; Lin Liu; Xinquan Zhang (Plant and Soil, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Selective recovery of lithium from spent lithium-ion batteries via mild hydrothermal driven Lewis acid-base reaction in aqua solution - Weiguang Lv; Jin Zhang; Yunpeng Liu; Jiao Lin; Xiaohong Zheng; Wenyi Yan; Hongbin Cao; Yi Zhang; Zhi Sun (Resources, Conservation and Recycling, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Double-shelled NiS/SnS@N-doped carbon nanoboxes engineered from NiSn(OH)6 cube templates for advanced sodium-ion battery anodes - Bo Yan; Lichen Lin; Hao Sun; Tiantian Zhang; Changqing Xu; Chang Sun; Lulu Zhang; Xuelin Yang (Chemical Engineering Journal, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Bibliometric evaluation of global research on eco-tourism - Han Lin; Yan Zhu; Zhoubao Sun; Pingping Wu; Jinjin Zhang (Environment, Development and Sustainability, 2023)

Rheological properties of chia seed gum extracted by high-speed shearing and its comparison with commercial polysaccharides - Lin Li; Jia-Nan Yan; Bin Lai; Ce Wang; Jin-Jian Sun; Hai-Tao Wu (Food Hydrocolloids, 2023)

Identification of circRNAs and circRNA-mRNA network of Epinephelus coioides during Singapore grouper iridovirus infection - Yi-Jie Cai; Wei Huang; Liang-Yuan Zhu; Yun-Xiang Lin; Cui-Fen Huang; Wen-Feng Yang; Jia-Lin Zhou; Jun-De Dong; Wei-Hua Zhou; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Synergistic effect between monophosphine species for regioselective hydroformylation of olefin with CO2 - Guoqing Wang; Miao Jiang; Zhao Sun; Leilei Qian; Guangjun Ji; Lei Ma; Cunyao Li; Zhaozhan Wang; Yong Yang; Xiangsong Lin; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Knockdown of LIMD2 inhibits the progression of ovarian carcinoma through ERK1/2 pathway - Haiyang Hu; Yanan Wang; Yan Dong; Lin Wang; Yahui Chen; Yan Zhou; Lin Sun (Molecular Biology Reports, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Packed OV-SnO2-Sb bead-electrodes for enhanced electrocatalytic oxidation of micropollutants in water - Chao Yang; Lin Lin; Shanshan Shang; Shengshou Ma; Feiyun Sun; Kaimin Shih; Xiao-yan Li (Water Research, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Novel and legacy brominated flame retardants in snakes and frogs: Tissue distribution, biomagnification, and maternal transfer - Guanzhen Sun; Xinyu Du; Yan Wu; Ge Yin; Luting Chen; Xiaojun Liu; Yihui Zhou; Yanling Qiu; Tian Lin (Science of The Total Environment, 2023)

Corrigendum to ‘Maternal circadian disruption before pregnancy impairs the ovarian function of female offspring in mice’ [Sci Total Environ. 2023 Mar 15;864:161161] - Yajie Guan; Manlin Xu; Zhe Zhang; Chuanming Liu; Jidong Zhou; Fei Lin; Junshun Fang; Yang Zhang; Qiuling Yue; Xin Zhen; Guijun Yan; Haixiang Sun; et al. (Science of The Total Environment, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

An optical study of the combustion and flame development of ammonia-diesel dual-fuel engine based on flame chemiluminescence - Wanchen Sun; Wenpeng Zeng; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu; Fei Wu (Fuel, 2023)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

Genome-wide DNA methylation landscape of four Chinese populations and epigenetic variation linked to Tibetan high-altitude adaptation - Zeshan Lin; Yan Lu; Guoliang Yu; Huajing Teng; Bao Wang; Yajun Yang; Qinglan Li; Zhongsheng Sun; Shuhua Xu; Wen Wang; Peng Tian (Science China Life Sciences, 2023)

A pruned feed-forward neural network (pruned-FNN) approach to measure air pollution exposure - Xi Gong; Lin Liu; Yanhong Huang; Bin Zou; Yeran Sun; Li Luo; Yan Lin (Environmental Monitoring and Assessment, 2023)

Earthworms enhance the inhibition efficiency of 3,4-dimethylpyrazole phosphate on soil nitrification by altering soil AOB communities and gut denitrifier communities - Bing-Jie Jin; Xi-Peng Liu; Miao Zhang; Yan Hu; Cheng-Liang Sun; Gang Li; Yong-Guan Zhu; Xian-Yong Lin (Biology and Fertility of Soils, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Speed and energy optimization method for the inland all-electric ship in battery-swapping mode - Yan Zhang; Lin Sun; Tianyuan Fan; Fan Ma; Yiyong Xiong (Ocean Engineering, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Microbial iron reduction activating sodium percarbonate for improving the dewaterability of iron-rich sludge - Lianpeng Sun; Chuanhan Chen; Siru Zhou; Weifang Yuan; Hui Lu; Hao Wang; Xinzhe Zhu; Huanzhong Deng; Xiao-yan Li; Lin Lin; Ruo-hong Li (Chemical Engineering Journal, 2023)

Ultralow loaded waste polystyrene derived hyper-cross-linked polymer for incineration flue gas demercuration: Synergistic effect of transition metal and halogen species - Yifan Xu; Limin Liu; Yueqing Xu; Xiaofei Yan; Cheng Zhang; Zifei Sun; Xiaochen Lin; Yufeng Duan; Houhu Zhang (Chemical Engineering Journal, 2023)

Integrated metabolomics and transcriptomics analyses reveal the key genes regulating differential metabolites of longissimus dorsi muscle in castrated South Sichuan black goats (Capra hircus) - Nanchi Zhang; Feng Xu; Li Wang; Quzhe Emu; Yong Wei; Lin Zhang; Yuan Xu; Jingsheng Fan; Yan Sun; Shuobu Shama; Hongyan Zhou; Chunmei Li; et al. (Functional & Integrative Genomics, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Association of the components of ambient fine particulate matter (PM2.5) and chronic kidney disease prevalence in China - Xingyuan Zhang; Jiayi Tao; Fang Lei; Tao Sun; Lijin Lin; Xuewei Huang; Peng Zhang; Yan-Xiao Ji; Jingjing Cai; Xiao-Jing Zhang; Hongliang Li (Journal of Environmental Management, 2023)

Designing low-carbon cement-free binders for stabilization/solidification of MSWI fly ash - Chen Sun; Weizhe Ge; Yuying Zhang; Lei Wang; Yan Xia; Xiaoqing Lin; Qunxing Huang; Shengyong Lu; Daniel C.W. Tsang; Jianhua Yan (Journal of Environmental Management, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Anaerobic membrane bioreactor for the treatment of high-strength waste/wastewater: A critical review and update - Zijing An; Junjie Zhu; Min Zhang; Yan Zhou; Xiaomei Su; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

A stabilizing benders decomposition method for the accessibility-oriented charging station location problem - Maocan Song; Lin Cheng; Huimin Ge; Yan Li; Chao Sun (Sustainable Cities and Society, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Succession and environmental response of sediment bacterial communities in the Liao River Estuary at the centenary scale - Zining Guo; Yan Li; Mengqi Shao; Tongxin Sun; Mengping Lin; Tie Zhang; Ke Hu; Hongchen Jiang; Xiangyu Guan (Marine Environmental Research, 2023)

Microwave-induced preparation of MgO-loaded N-rich porous biochar from marine biomass for efficient CO2 capture and mechanism exploration via theoretical calculation - Juan Luo; Yi Chen; Xi Zhang; Rui Ma; Huimin Huang; Shichang Sun; Junhao Lin; Feng Yan; Jiyun Xu (Journal of Cleaner Production, 2023)

Establishing highly efficient absorptive and catalytic network for depolarized high-stability lithium-sulfur batteries - Jianan Wang; Xin Chen; Zhenyu Wang; Changzheng Lin; Shiyi Sun; Jianwei Liu; Yunpeng Liu; Qianyue Ma; Ling Wang; Kai Yang; Jiangtao Feng; Xi Wang; et al. (Chemical Engineering Journal, 2023)

Correction to: Low-carbon stabilization/solidification of municipal solid waste incineration fly ash - Chen Sun; Lei Wang; Xiaoqing Lin; Shengyong Lu; Qunxing Huang; Jianhua Yan (Waste Disposal & Sustainable Energy, 2023)

Knowledge Map and Global Trends in Root Exudates Research from 2012 to 2021: a Bibliometric Analysis - Xin Zheng; Dongming Chen; Jiqiong Zhou; Qian Huang; Xingpeng Hu; Zhuxin Deng; Xuemei Fang; Feida Sun; Junming Zhao; Xiao Ma; Congyu Ma; Xinrui Yan; et al. (Journal of Soil Science and Plant Nutrition, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

OsCIP1, a secreted protein, binds to and stabilizes OsCR4 to promote aleurone layer development, seed germination and early seedling growth in rice - Lin-Lin Yan; Jing Mi; Can-Can Shen; Rong Qian; Jiao Wang; Cui-Xia Pu; Ying Sun (Plant Science, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Gut Microbiota in Children with Hand Foot and Mouth Disease on 16S rRNA Gene Sequencing - Yan Zhuang; Yiyan Lin; Hongxia Sun; Zaiting Zhang; Tao Wang; Rongjun Fan; Lu Han (Current Microbiology, 2023)

Morphological and physicochemical characteristics, biological functions, and biomedical applications of diatom frustule - Chenfei Yang; Chao Feng; Yuhang Li; Zheng Cao; Yan Sun; Xiaohui Li; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Surface wave exploration technology for the tunnel overlying strata with vehicle vibration source - Yuefeng Yan; Chengyu Sun; Tengfei Lin; Jiao Wang; Xixi Huang; Qixin Ge; Dayong Zhou (Tunnelling and Underground Space Technology, 2023)

Co-Fe synergy in CoxFe1-xWO4: The new type peroxymonosulfate activator for sulfamethoxazole degradation - Feng Zhang; Hai-Ning Yan; Yuan-Feng Jin; Lin-Feng Zhai; Min Sun (Chemical Engineering Journal, 2023)

Maternal circadian disruption before pregnancy impairs the ovarian function of female offspring in mice - Yajie Guan; Manlin Xu; Zhe Zhang; Chuanming Liu; Jidong Zhou; Fei Lin; Junshun Fang; Yang Zhang; Qiuling Yue; Xin Zhen; Guijun Yan; Haixiang Sun; et al. (Science of The Total Environment, 2023)

Discovery of novel ascorbic acid derivatives and other metabolites in fruit of Rosa roxburghii Tratt through untargeted metabolomics and feature-based molecular networking - Yaqi Zhang; Xiqing Bian; Guanyu Yan; Baoqing Sun; Wen Miao; Mingzheng Huang; Na Li; Jian-Lin Wu (Food Chemistry, 2023)

Citral and cinnamaldehyde – Pickering emulsion stabilized by zein coupled with chitosan against Aspergillus. spp and their application in food storage - Yan Wang; Jiayu Xu; Wei Lin; Jian Wang; Hao Yan; Peilong Sun (Food Chemistry, 2023)

Storage stability of scallop (Patinopecten yessoensis) male gonad hydrolysates/κ-carrageenan composite hydrogels embeded curcumin - Jia-Nan Yan; Xin-Yu Jiang; Lin Li; Wen Sun; Bin Lai; Hai-Tao Wu (Food Hydrocolloids, 2023)

CotA laccase from Bacillus licheniformis ZOM-1 effectively degrades zearalenone, aflatoxin B1 and alternariol - Fan Sun; Dianzhen Yu; Haiyan Zhou; Huikang Lin; Zheng Yan; Aibo Wu (Food Control, 2023)

Locking-DNA network regulated CRISPR-Cas12a fluorescent aptasensor based on hollow flower-like magnetic MoS2 microspheres for sensitive detection of sulfadimethoxine - Yan Lv; Yuhan Sun; Imran Mahmood Khan; Qiaofeng Li; You Zhou; Lin Yue; Yin Zhang; Zhouping Wang (Chemical Engineering Journal, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Hierarchical multiphase (Ni, Co)-Se with adjustable interlayer distance derived from reconstructed ZIF-L for enhanced hybrid-supercapacitors - Lin Sun; Yu Liu; Bifu Luo; Fangrong Yan; Xiaoying Liu; Fangfang Zhu; Weidong Shi (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Urban park use and self-reported physical, mental, and social health during the COVID-19 pandemic: An on-site survey in Beijing, China - Di Lin; Yan Sun; Yue Yang; Yi Han; Chengyang Xu (Urban Forestry & Urban Greening, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Diet-rich in wheat bran modulates tryptophan metabolism and AhR/IL-22 signalling mediated metabolic health and gut dysbacteriosis: A novel prebiotic-like activity of wheat bran - Tao Yan; Lin Shi; Tianqi Liu; Xiangnan Zhang; Minmin Yang; Wen Peng; Xiaomin Sun; Lijing Yan; Xiaoshuang Dai; Xinbing Yang (Food Research International, 2023)

Dual-targeting celecoxib nanoparticles protect intestinal epithelium and regulate macrophage polarization for ulcerative colitis treatment - Ruijie Chen; Xinlu Lin; Qian Wang; Xingsi An; Xinyu Zhao; Yujie Lin; Tuyue Sun; Chenyang Yan; Aimin Cai; Weilan Cao; Youting Zhang; Qing Yao; et al. (Chemical Engineering Journal, 2023)

Lamellar-structured anodes based on lithiophilic gradient enable dendrite-free lithium metal batteries with high capacity loading and fast-charging capability - Yucheng Liu; Chuang Sun; Yuhao Lu; Xiaoping Lin; Maohua Chen; Yuansen Xie; Chao Lai; Wen Yan (Chemical Engineering Journal, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

Improving yield and nitrogen use efficiency of hybrid indica rice through optimizing nitrogen application strategies in the rice season under different rotation patterns - YongJian Sun; Dan Lin; YuanYuan Sun; FengJun Yan; Peng Ma; ChangChun Guo; FeiJie Li; ZhiYuan Yang; FuXian Xu; Jun Ma (Paddy and Water Environment, 2023)

Inheritance and Development: The Evolution and Overview of China’s Fisheries Legal System - Wei Wu; Yang Liu; Zhaobin Pei; Yan Lin; Xin Sun; Jiaqi Xing; Yuwei Wang; Yu Liu (Fishes, 2022)
China’s legal system governing fisheries in China has been stable during development. In line with China’s national conditions and the spirit of the times, they have adhered to the concept of green development and maintaining the sustainable development of fishery production activities. Studying the history of Chinese fishery law is beneficial for the world to understand the evolution of this legislation and is a better gateway for the world to understand fisheries law with Chinese characteristics. Fishery, in this context, refers to fishing and fish farming. In China, fisheries are under the management of the Ministry of Agriculture and Rural Affairs, while fisheries enforcement has a special law enforcement department for collaborative management. Therefore, both fishing and fish farming in China’s fisheries industry belong to the category of agriculture. This is different from the West and is precisely what makes China unique. This paper explores the Chinese fishery legal and general legal systems by investigating policy guidelines, laws, and regulations on China’s fishery industry since 1949. Furthermore, it analyzes the development process of fisheries. Organizing the development status of China’s fishery legal and regulatory system analyzes the problems of fishery production control and development, searches for paths and methods to solve the practical problems, and finally, makes a reasonable outlook on the development prospect of China’s fishery.

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Development of diagnostic molecular markers to differentiate sharp eyespot and Fusarium crown rot isolates collected from common wheat fields in China - Yan Ren; Yue Wang; Li-yan Wang; Xia-Lei Lv; Ti Liu; Jing-yun Nie; Peng Guo; Lin Ma; Xiao-nan Sun; Feng Chen (Phytoparasitica, 2022)

Sphingomicrobium nitratireducens sp. nov., isolated from a tidal flat in Guangxi - Hao You; Lin Xu; Yan-Hui Kong; Cong Sun; Peng Zhou; Xue-Wei Xu (Archives of Microbiology, 2022)

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

Reciprocal modulation between cigarette smoking and internet gaming disorder on participation coefficient within functional brain networks - Xianxin Qiu; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Hao Lei; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2022)

Effect of straw biochar from different crops on growth and nutrient uptake by peach (Prunus davidiana) seedlings - Qin Liu; Haoran Zhang; Yan Wang; Jing Sun; Dong Chen; Meiyan Tu; Lijin Lin (Acta Physiologiae Plantarum, 2022)

Potential and Distribution of Natural Gas Hydrate Resources in the South China Sea - Pibo Su; Lin Lin; Yaoyao Lv; Jinqiang Liang; Yunbao Sun; Wei Zhang; Huice He; Baiquan Yan; Zhanhuai Ji; Lifeng Wang; Feifei Wang; Mengya Cai (Journal of Marine Science and Engineering, 2022)
The amount of natural gas contained in the world’s gas hydrate accumulations is enormous, but these estimates remain highly speculative. So far, it is still challenging to locate spatial distribution of marine gas hydrate and quantitatively characterize the evaluation parameters and systematic improvement of evaluation systems. Considering the systematic review of the key accumulation factors, such as heat flow, deposition rate and total organic carbon in the typical passive continental margin, the evaluation results of global marine gas hydrate resources were analyzed based on the characteristics of gas hydrate geology, geophysics and geochemistry anomalies in the South China Sea. We analyze the problems on the evaluation of marine gas hydrate resources, probing into the geological characteristics and distribution laws of marine gas hydrate resources in the South China Sea, and estimate the parameters for in-place resource evaluation, in which the volume method based on Monte Carlo probability was used to evaluate the gas hydrate potential resources in the South China Sea. The probability distribution ranges from 37.6 billion (with 90% probability) to 117.7 billion (with 10% probability) tons of oil equivalent, with an expected value of 74.4 billion tons of oil equivalent. The study results show that the gas hydrate resource density in the South China Sea is similar to that in the typical sea areas, and the estimated global resources are basically consistent with the assessment results at this stag; this shows that the South China Sea has great potential for gas hydrate resources. The research results can provide guidance for the evaluation of global climate change and the exploration and development of hydrate resources.

The fibroblast growth factor receptor antagonist SSR128129E inhibits fat accumulation via suppressing adipogenesis in mice - Xinzhi Zhang; Xin Wen; Geng Hu; Qiang Zhang; Qianying Sun; Yanxin Jia; Yan Liu; Hai Lin; Haifang Li (Molecular Biology Reports, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Effects of ambient air pollution on glycosylated hemoglobin: a systematic review and meta-analysis - Li Tian; Mengqi Sun; Lisen Lin; Yan Wang; Yang Yu; Junchao Duan; Zhiwei Sun (Environmental Science and Pollution Research, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Experimental study of energy and frequency characteristics of acoustic emissions induced from tensile and shear cracks in tunnel rockburst process - Yan-Bo Zhang; Peng Liang; Xu-Long Yao; Lin Sun; Bao-Zhu Tian; Xiang-Xin Liu (European Journal of Environmental and Civil Engineering, 2022)

Low-carbon stabilization/solidification of municipal solid waste incineration fly ash - Chen Sun; Lei Wang; Xiaoqing Lin; Shengyong Lu; Qunxing Huang; Jianhua Yan (Waste Disposal & Sustainable Energy, 2022)

Characterizing sediment bacterial community and identifying the biological indicators in a seawater-freshwater transition zone during the wet and dry seasons - Yongbin Li; Duanyi Huang; Weimin Sun; Xiaoxu Sun; Geng Yan; Wenlong Gao; Hanzhi Lin (Environmental Science and Pollution Research, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Soil phosphorus drives plant trait variations in a mature subtropical forest - Erqian Cui; Ruiling Lu; Xiaoni Xu; Huanfa Sun; Yang Qiao; Jiaye Ping; Shuying Qiu; Yihua Lin; Jiehuan Bao; Yutong Yong; Zemei Zheng; Enrong Yan; et al. (Global Change Biology, 2022)
Earth system models are implementing soil phosphorus dynamic and plant functional traits to predict functional changes in global forests. However, the linkage between soil phosphorus and plant traits lacks empirical evidence, especially in mature forests. Here, we examined the soil phosphorus constraint on plant functional traits in a mature subtropical forest based on observations of 9943 individuals from 90 species in a 5‐ha forest dynamic plot and 405 individuals from 15 species in an adjacent 10‐year nutrient‐addition experiment. We first confirmed a pervasive phosphorus limitation on subtropical tree growth based on leaf N:P ratios. Then, we found that soil phosphorus dominated multidimensional trait variations in the 5‐ha forest dynamic plot. Soil phosphorus content explained 44% and 53% of the variance in the traits defining the main functional space across species and communities, respectively. Lastly, we found much stronger phosphorus effects on most plant functional traits than nitrogen at both species and community levels in the 10‐year nutrient‐addition experiment. This study provides evidence for the consistent pattern of soil phosphorus constraint on plant trait variations between the species and community levels in a mature evergreen broadleaf forest in the East Asian monsoon region. These findings shed light on the predominant role of soil phosphorus on plant functional trait variations in mature subtropical forests, providing new insights for models to incorporate soil phosphorus constraint in predicting future vegetation dynamics.

Berberisides A-D: three novel prenylated benzoic acid derivatives and a clerodane glycoside from Berberis tsarica aherndt. - Zhao-Yue Dong; Qing-Hong Zeng; Lin Wei; Xin Guo; Yan Sun; Fan-Cheng Meng; Guo-Wei Wang; Xiao-Zhong Lan; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Description of Aureibaculum luteum sp. nov. and Aureibaculum flavum sp. nov. isolated from Antarctic intertidal sediments - Xiao-yan He; Ning-hua Liu; Chao-yi Lin; Mei-ling Sun; Xiu-lan Chen; Yu-zhong Zhang; Yu-qiang Zhang; Xi-ying Zhang (Antonie van Leeuwenhoek, 2022)

Perchlorate contamination of tea leaves and a corresponding probabilistic dietary risk assessment using Monte Carlo simulation - Qinghua Yao; Sun-an Yan; Wenjing Liu; Minmin Huang; Qiu Lin (Food Additives & Contaminants: Part A, 2022)

Full-Length Transcriptome of Red Swamp Crayfish Hepatopancreas Reveals Candidate Genes in Hif-1 and Antioxidant Pathways in Response to Hypoxia-Reoxygenation - Yu Xu; Hai Lin; Weihui Yan; Jiajia Li; Mengling Sun; Jiaping Chen; Zhiqiang Xu (Marine Biotechnology, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Aquimarina algicola sp. nov., isolated from the surface of a marine red alga - Xun-Ke Sun; Yan-Lin Zhong; Xu-Yang Chen; Guan-Jun Chen; Zong-Jun Du (Archives of Microbiology, 2021)

Synthesis of 3D graphene-based materials and their applications for removing dyes and heavy metals - Hefei Sun; Yan Lin; Hagio Takeshi; Xinze Wang; Deyi Wu; Yanqin Tian (Environmental Science and Pollution Research, 2021)

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Association between population density and infection rate suggests the importance of social distancing and travel restriction in reducing the COVID-19 pandemic - Heliang Yin; Tong Sun; Lan Yao; Yan Jiao; Li Ma; Lin Lin; J Carolyn Graff; Lotfi Aleya; Arnold Postlethwaite; Weikuan Gu; Hong Chen (Environmental Science and Pollution Research, 2021)

Identification of three seagrass species in coral reef ecosystem by using multiple genes of DNA barcoding - Xiancheng Lin; Junde Dong; Qingsong Yang; Weiguo Zhou; Yan Wang; Ying Zhang; Manzoor Ahmad; Yingting Sun; Youshao Wang; Juan Ling (Ecotoxicology, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Experimental Research on Adsorption Kinetic Characteristics of CH4, CO2, and N2 in Coal from Junggar Basin, China, at Different Temperatures - Wanjie Sun; Haifei Lin; Shugang Li; Xiangguo Kong; Hang Long; Min Yan; Yang Bai; Jiamin Tian (Natural Resources Research, 2021)

Alterinioella nitratireducens gen. nov., sp. nov., Isolated from Seawater in the West Pacific Ocean - Yan-Hui Kong; Cong Sun; Li-Li Guo; Lin Xu; Yue-Hong Wu; Xue-Wei Xu (Current Microbiology, 2021)

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Fertilization alters protistan consumers and parasites in crop‐associated microbiomes - Anqi Sun; Xiao‐Yan Jiao; Qinglin Chen; Pankaj Trivedi; Zixin Li; Fangfang Li; Yong Zheng; Yongxin Lin; Hang‐Wei Hu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Crop plants carry an enormous diversity of microbiota that provide massive benefits to hosts. Protists, as the main microbial consumers and a pivotal driver of biogeochemical cycling processes, remain largely understudied in the plant microbiome. Here, we characterized the diversity and composition of protists in sorghum leaf phyllosphere, and rhizosphere and bulk soils, collected from an 8‐year field experiment with multiple fertilization regimes. Phyllosphere was an important habitat for protists, dominated by Rhizaria, Alveolata and Amoebozoa. Rhizosphere and bulk soils had a significantly higher diversity of protists than the phyllosphere, and the protistan community structure significantly differed among the three plant–soil compartments. Fertilization significantly altered specific functional groups of protistan consumers and parasites. Variation partitioning models revealed that soil properties, bacteria and fungi predicted a significant proportion of the variation in the protistan communities. Changes in protists may in turn significantly alter the compositions of bacterial and fungal communities from the top‐down control in food webs. Altogether, we provide novel evidence that fertilization significantly affects the functional groups of protistan consumers and parasites in crop‐associated microbiomes, which have implications for the potential changes in their ecological functions under intensive agricultural managements.

Fluorine enrichment of vegetables and soil around an abandoned aluminium plant and its risk to human health - Lingling He; Chenglong Tu; Shouyang He; Jiulai Long; Ya Sun; Yan Sun; Changhu Lin (Environmental Geochemistry and Health, 2021)

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

Engrafted primary type-2 astrocytes improve the recovery of the nigrostriatal pathway in a rat model of Parkinson's disease - Yanyun Sun; Xiao-jun Lu; Xinghui Fu; Ye Zhang; Yan Zhan; Jiabing Liu; Lingxia Zhao; Chun-lin Xia (Molecular and Cellular Biochemistry, 2021)

Genotyping-by-sequencing to determine the genetic structure of a Tibetan medicinal plant Swertia mussotii Franch. - Yan Qiao; Fengxian Guo; Naxin Huo; Lin Zhan; Jiaqing Sun; Xixi Zuo; Zeguang Guo; Yong Q. Gu; Yi Wang; Yue Liu (Genetic Resources and Crop Evolution, 2021)

Sex-specific effects of cigarette smoking on caudate and amygdala volume and resting-state functional connectivity - Fuchun Lin; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Yan Zhou; Hao Lei (Brain Imaging and Behavior, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Ferrous iron-induced increases in capitate glandular trichome density and upregulation of CbHO-1 contributes to increases in blinin content in Conyza blinii - Tianrun Zheng; Maojia Wang; Junyi Zhan; Wenjun Sun; Qin Yang; Zhiyi Lin; Tongliang Bu; Zizhong Tang; Chenglei Li; Jun Yan; Zhi Shan; Hui Chen (Planta, 2020)

MicroRNA-761 modulates foam cell formation and inflammation through autophagy in the progression of atherosclerosis - Chao Wang; Wei Yang; Xiaofei Liang; Wei Song; Jing Lin; Yan Sun; Xiuru Guan (Molecular and Cellular Biochemistry, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Mu-Opioid Receptors Expressed in Glutamatergic Neurons are Essential for Morphine Withdrawal - Xin-Yan Zhang; Qing Li; Ye Dong; Wei Yan; Kun Song; Yong-Qin Lin; Yan-Gang Sun (Neuroscience Bulletin, 2020)

A novel freshwater cyanophage vB_MelS-Me-ZS1 infecting bloom-forming cyanobacterium Microcystis elabens - Wei Lin; Dengfeng Li; Zhitong Sun; Yigang Tong; Xiaojun Yan; Chunlin Wang; Xianglilan Zhang; Guangqian Pei (Molecular Biology Reports, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Dietary risk assessment of pesticide residues on Tremella fuciformis Berk (snow fungus) from Fujian Province of China - Qinghua Yao; Sun-an Yan; Hanzhen Chen; Jie Li; Qiu Lin (Food Additives & Contaminants: Part A, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Involvement of the JNK signaling in granular corneal dystrophy by modulating TGF-β-induced TGFBI expression and corneal fibroblast apoptosis - Danyao Nie; Xinhua Liu; Yuan Wang; Wenling He; Ming Li; Yun Peng; Jing Zhang; Liangnan Sun; Zonghui Yan; Lin Ye (In Vitro Cellular & Developmental Biology - Animal, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Age- and Nicotine-Associated Gene Expression Changes in the Hippocampus of APP/PS1 Mice - Jie Yang; Yan Long; De-Mei Xu; Bing-Lin Zhu; Xiao-Juan Deng; Zhen Yan; Fei Sun; Guo-Jun Chen (Journal of Molecular Neuroscience, 2019)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Sex differences in resting-state cerebral activity alterations in internet gaming disorder - Yawen Sun; Yao Wang; Xu Han; Wenqing Jiang; Weina Ding; Mengqiu Cao; Yasong Du; Fuchun Lin; Jianrong Xu; Yan Zhou (Brain Imaging and Behavior, 2019)

QTL analysis of nodule traits and the identification of loci interacting with the type III secretion system in soybean - Jingyi Zhu; Jinhui Wang; Qingying Li; Jieqi Wang; Yang Liu; Jianyi Li; Lin Chen; Yan Shi; Shuping Li; Yongqian Zhang; Xueying Liu; Chao Ma; et al. (Molecular Genetics and Genomics, 2019)

Matrix metalloproteinase 9 induces keratinocyte apoptosis through FasL/Fas pathway in diabetic wound - Ying Liang; Chuan Yang; Yongqing Lin; Yasir Parviz; Kan Sun; Wei Wang; Meng Ren; Li Yan (Apoptosis, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Large-scale analysis of small RNAs derived from traditional Chinese herbs in human tissues - Fengming Huang; Jianchao Du; Zhu Liang; Zhichao Xu; Jiantao Xu; Yan Zhao; Yexuan Lin; Song Mei; Quan He; Jindong Zhu; Qiang Liu; Yanxu Zhang; et al. (Science China Life Sciences, 2019)

Phylogenetic analysis of upland cotton MATE gene family reveals a conserved subfamily involved in transport of proanthocyanidins - Lei Xu; Zhi-Lin Shen; Wen Chen; Guo-Yang Si; Yan Meng; Ning Guo; Xu Sun; Yong-Ping Cai; Yi Lin; Jun-Shan Gao (Molecular Biology Reports, 2019)

Intraguild predation between Harmonia axyridis and Aphidius gifuensis: effects of starvation period, plant dimension and extraguild prey density - Xing-Lin Yu; Yi Feng; Wen-Yan Fu; Yuan-Xing Sun; Tong-Xian Liu (BioControl, 2019)

Responses of lipoxygenase, jasmonic acid, and salicylic acid to temperature and exogenous phytohormone treatments in Gracilariopsis lemaneiformis (Rhodophyta) - Sainan Hou; Lichun Lin; Yan Lv; Nianjun Xu; Xue Sun (Journal of Applied Phycology, 2018)

Comparative pharmacokinetics study of five alkaloids in rat plasma and related compound–herb interactions mechanism after oral administration of Shuanghua Baihe tablets - Xinyu Zhao; Yan Wang; Lu Zheng; Chengpeng Sun; Chao Wang; Haijian Cong; Ting Xiang; Lin Zhang; Houli Zhang; Sa deng; Baojing Zhang; Bin Wu; et al. (Natural Product Research, 2018)

Stability analysis of large-scale waste mounds with respect to consolidation effect - Shu Lin; Shuwang Yan; Zhaolin Jia; Liqiang Sun; Jia Li; Jingjing Zhang (European Journal of Environmental and Civil Engineering, 2018)

Estrogen deficiency compromised the β2AR-Gs/Gi coupling: implications for arrhythmia and cardiac injury - Hongjian Hou; Zhiwei Zhao; Jeremiah Ong’achwa Machuki; Lin Zhang; Yan Zhang; Lu Fu; Jinxia Wu; Yuyu Liu; Sian E. Harding; Hong Sun (Pflügers Archiv - European Journal of Physiology, 2018)

HAP1 Is Required for Endocytosis and Signalling of BDNF and Its Receptors in Neurons - Yoon Lim; Linda Lin-Yan Wu; Si Chen; Ying Sun; Swarna Lekha Vijayaraj; Miao Yang; Larisa Bobrovskaya; Damien Keating; Xiao-Jiang Li; Xin-Fu Zhou (Molecular Neurobiology, 2018)

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Eburicoic acid from Laetiporus sulphureus (Bull.:Fr.) Murrill attenuates inflammatory responses through inhibiting LPS-induced activation of PI3K/Akt/mTOR/NF-κB pathways in RAW264.7 cells - Junzhi Wang; Pan Zhang; Haibo He; Xinxin Se; Wenjun Sun; Beiyan Chen; Lin Zhang; Ximing Yan; Kun Zou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Two new flavans from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Shu-Sheng Huang; Ye-Er Liang; Jian-Bo Sun; Yan Ma; Bao Zeng; Simon Ming-Yuen Lee; Jian-Lin Lu (Natural Product Research, 2017)

Berry syndrome: a rare cardiac malformation with extra-cardiac findings - Jingya Li; Ya Yang; Xiaomin Duan; Lanzhong Jin; Lin Zheng; Xin Zhang; Haiyan Wei; Yan Sun; Xiaolin Zhang; Pei Li; Jiao Yang; Ning Ma; et al. (Science China Life Sciences, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

The improvement of M1 polarization in macrophages by glycopeptide derived from Ganoderma lucidum - Li-Xin Sun; Zhi-Bin Lin; Jie Lu; Wei-Dong Li; Yan-Dong Niu; Yu Sun; Chen-Yang Hu; Guo-Qiang Zhang; Xin-Suo Duan (Immunologic Research, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

Equisetum cf. oppositum (Equisetaceae) from the Paleocene-Eocene of Tibet in southwestern China and its paleoenvironmental implications - Guo-Lin Yang; Zi-Xi Wang; Jing-Wei Chen; De-Fei Yan; Bai-Nian Sun (Arabian Journal of Geosciences, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Metabolomic analysis of competent larvae and juvenile veined rapa whelks (Rapana venosa) - Hao Song; Li-Yuan Sun; Zheng-Lin Yu; Li-Na Sun; Dong-Xiu Xue; Tao Zhang; Hai-Yan Wang (Marine Biology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Characterization of Rebound Depolarization in Neurons of the Rat Medial Geniculate Body In Vitro - Xin-Xing Wang; Yan Jin; Hui Sun; Chunlei Ma; Jinsheng Zhang; Ming Wang; Lin Chen (Neuroscience Bulletin, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Mitigation of cadmium and arsenic in rice grain by applying different silicon fertilizers in contaminated fields - Hong-Yan Wang; Shi-Lin Wen; Peng Chen; Lu Zhang; Kuang Cen; Guo-Xin Sun (Environmental Science and Pollution Research, 2016)

Characterization of Rebound Depolarization in Neurons of the Rat Medial Geniculate Body In Vitro - Xin-Xing Wang; Yan Jin; Hui Sun; Chunlei Ma; Jinsheng Zhang; Ming Wang; Lin Chen (Neuroscience Bulletin, 2016)

Isolation, purification, and identification of antialgal substances in green alga Ulva prolifera for antialgal activity against the common harmful red tide microalgae - Ying-ying Sun; Hui Wang; Gan-lin Guo; Yin-fang Pu; Bin-lun Yan; Chang-hai Wang (Environmental Science and Pollution Research, 2016)

Complete Genome of a Novel Pseudoalteromonas Phage PHq0 - Duo-bing Wang; Yan Li; Meng-qi Sun; Jin-peng Huang; Hong-bing Shao; Qi-lin Xin; Min Wang (Current Microbiology, 2016)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

SZC017, a novel oleanolic acid derivative, induces apoptosis and autophagy in human breast cancer cells - Lei Gao; Yan Wang; Zhen Xu; Xiaorui Li; Jingjun Wu; Shumin Liu; Peng Chu; Zhengwu Sun; Bin Sun; Yuan Lin; Jinyong Peng; Guozhu Han; et al. (Apoptosis, 2015)

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression - Ying Wu; Tingting Jiang; Yue Sun; Zeyang Wang; Guizhen Guo; Shuai Sun; Jie Wang; Ning Li; Zhenhui Wang; Di Zhang; Yan Bai; Yang Gao; et al. (Plant Molecular Biology Reporter, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Impacts of ecological restoration and human activities on habitat of overwintering migratory birds in the wetland of Poyang Lake, Jiangxi Province, China - Chuan-zhun Sun; Lin Zhen; Chao Wang; Bang-you Yan; Xiao-chang Cao; Rui-zi Wu (Journal of Mountain Science, 2015)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

A large-scale breeding experiment and observations on development of Cyanea nozakii (Scyphozoa, Cyaneidae) from fertilized eggs to larval medusae - Chun-sheng Liu; Zhi-meng Zhuang; Si-qing Chen; Jing-ping Yan; Chang-lin Liu; Jian-ming Sun (Hydrobiologia, 2015)

Green alga Ulva pertusa—a new source of bioactive compounds with antialgal activity - Sun Ying-ying; Wang Hui; Guo Gan-lin; Pu Yin-fang; Yan Bin-lun; Wang Chang-hai (Environmental Science and Pollution Research, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

Phenology-based classification of vegetation cover types in Northeast China using MODIS NDVI and EVI time series - Enping Yan; Guangxing Wang; Hui Lin; Chaozong Xia; Hua Sun (International Journal of Remote Sensing, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

The cellular community in the intestine of the shrimp Penaeus penicillatus and its culture environments - Chun-zhong Wang; Guo-rong Lin; Tao Yan; Zhi-peng Zheng; Bin Chen; Fu-lin Sun (Fisheries Science, 2014)

Erratum to: Genome-wide analysis of DNA methylation in an APP/PS1 mouse model of Alzheimer’s disease - Lin Cong; Jianping Jia; Wei Qin; Yan Ren; Yongxin Sun (Acta Neurologica Belgica, 2014)

Genome-wide analysis of DNA methylation in an APP/PS1 mouse model of Alzheimer’s disease - Lin Cong; Jianping Jia; Wei Qin; Yan Ren; Yongxin Sun (Acta Neurologica Belgica, 2014)

Platelet-derived growth factor-BB induces matrix metalloproteinase-2 expression and rat vascular smooth muscle cell migration via ROCK and ERK/p38 MAPK pathways - Ying Cui; Yin-Wei Sun; Hai-Shuang Lin; Wei-Min Su; Yan Fang; Ying Zhao; Xiao-Qing Wei; Yuan-Hua Qin; Kazuhiro Kohama; Ying Gao (Molecular and Cellular Biochemistry, 2014)

An analysis of the resilience capacity of soils in North China: a study on land subsidence treatment - Xiu-yan Wang; Lin Sun; Zhi-liang Wang; Chang-li Liu; Yun Zhang (Bulletin of Engineering Geology and the Environment, 2014)

Evidences for B6C3-Tg (APPswe/PSEN1dE9) Double-Transgenic Mice Between 3 and 10 Months as an Age-Related Alzheimer’s Disease Model - Zhiyong Zhong; Lin Yang; Xiansheng Wu; Wei Huang; Jiarong Yan; Shenglai Liu; Xia Sun; Ke Liu; Huangquan Lin; Shaosong Kuang; Xiaojiang Tang (Journal of Molecular Neuroscience, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Unpalatable weed Stellera chamaejasme L. provides biotic refuge for neighboring species and conserves plant diversity in overgrazing alpine meadows on the Tibetan Plateau in China - Wei Cheng; Geng Sun; Lin-fang Du; Yan Wu; Qun-ying Zheng; Hong-xuan Zhang; Lin Liu; Ning Wu (Journal of Mountain Science, 2014)

CD24 mediates gastric carcinogenesis and promotes gastric cancer progression via STAT3 activation - Ying-Chao Wang; Ji-Lin Wang; Xuan Kong; Tian-Tian Sun; Hao-Yan Chen; Jie Hong; Jing-Yuan Fang (Apoptosis, 2014)

Probing the distribution and contamination levels of 10 trace metal/metalloids in soils near a Pb/Zn smelter in Middle China - Zhonggen Li; Xinbin Feng; Xiangyang Bi; Guanghui Li; Yan Lin; Guangyi Sun (Environmental Science and Pollution Research, 2014)

Genetic diversity and hybridization of Pulsatilla tongkangensis based on the nrDNA ITS region sequence - Yan-Lin Sun; Wan-Geun Park; Hyun-Kyung Oh; Soon-Kwan Hong (Biologia, 2014)

Identification of MHC class I sequences in four species of Macaca of China - Xiang Yan; Aixue Li; Lin Zeng; Yuhua Cao; Jianbin He; Longbao Lv; Lihua Sui; Huahu Ye; Junwen Fan; Xiaoxia Cui; Zhaozeng Sun (Immunogenetics, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Oxidative stress and MAPK involved into ATF2 expression in immortalized human urothelial cells treated by arsenic - Shengnan Liu; Fei Wang; Ling Yan; Lin Zhang; Yingli Song; Shuhua Xi; Jing Jia; Guifan Sun (Archives of Toxicology, 2013)

Hippocampal CLOCK protein participates in the persistence of depressive-like behavior induced by chronic unpredictable stress - Wen-Gao Jiang; Su-Xia Li; Jian-Feng Liu; Yan Sun; Shuang-Jiang Zhou; Wei-Li Zhu; Jie Shi; Lin Lu (Psychopharmacology, 2013)

Wogonin enhances antitumor activity of tumor necrosis factor-related apoptosis-inducing ligand in vivo through ROS-mediated downregulation of cFLIPL and IAP proteins - Lan Yang; Qiong Wang; Daoxia Li; Yuqiong Zhou; Xuelian Zheng; Hong Sun; Jiaqi Yan; Lin Zhang; Yong Lin; Xia Wang (Apoptosis, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Sensitivity of Translation Initiation Factor eIF1 as a Molecular Target of Salt Toxicity to Sodic-Alkaline Stress in the Halophytic Grass Leymus chinensis - Yan-Lin Sun; Soon-Kwan Hong (Biochemical Genetics, 2013)

The satellite reversion of dissolved organic carbon (DOC) based on the analysis of the mixing behavior of DOC and colored dissolved organic matter: the East China Sea as an example - Qiong Liu; Delu Pan; Yan Bai; Kai Wu; Chen-Tung Arthur Chen; Jun Sun; Lin Zhang (Acta Oceanologica Sinica, 2013)

Agrobacterium tumefaciens-Mediated Transformation of the Halophyte Leymus chinensis (Trin.) - Yan-Lin Sun; Soon-Kwan Hong (Plant Molecular Biology Reporter, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Is the Evolution of Viviparity Accompanied by a Relative Increase in Maternal Abdomen Size in Lizards? - Yan-Yan Sun; Yu Du; Jing Yang; Tian-Bao Fu; Chi-Xian Lin; Xiang Ji (Evolutionary Biology, 2012)

Winter wheat mapping using temporal signatures of MODIS vegetation index data - Huasheng Sun; Aigong Xu; Hui Lin; Lianpeng Zhang; Yan Mei (International Journal of Remote Sensing, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Effect of Chitinase on Resistance to Fungal Pathogens in Sea Buckthorn, Hippophae rhamnoides, and Cloning of Class I and III Chitinase Genes - Yan-Lin Sun; Soon-Kwan Hong (Biochemical Genetics, 2012)

Drug-related cues exacerbate decision making and increase craving in heroin addicts at different abstinence times - Gui-Bin Wang; Xiao-Li Zhang; Li-Yan Zhao; Li-Li Sun; Ping Wu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Role of calcineurin in the VTA in rats behaviorally sensitized to methamphetamine - Jun Wang; Li-Li Sun; Wei-Li Zhu; Yan Sun; Jian-Feng Liu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

The proportions and variations of the light absorption coefficients of major ocean color components in the East China Sea - Hui Lei; Delu Pan; Yan Bai; Bangyi Tao; Jun Sun; Lin Zhang; Xuan Zhang (Acta Oceanologica Sinica, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

2,5-Hexanedione induces human ovarian granulosa cell apoptosis through BCL-2, BAX, and CASPASE-3 signaling pathways - Yan Sun; Yuan Lin; Hong Li; Jin Liu; Xiaohua Sheng; Wenchang Zhang (Archives of Toxicology, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Evaluation of Left Ventricular Twist in Acute Myocardial Infarction Patients Using Speckle Tracking Imaging - Da-lin Jia; Chun-yan Ma; Shuang Liu; Lu-fan Sun (Cell Biochemistry and Biophysics, 2011)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Synthesis and characterization of graft copolymer of chitosan and polyethylene glycol - Yan Zhao; Yiyi Sun; Zhihe Zang; Xiaohong Xu; Zhonglin Zhang; Ling Zhong; Wang Zan; Yan Zhao; Lin Sun (Molecular Biology Reports, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Mapping the self-interacting domains of TuMV HC-Pro and the subcellular localization of the protein - Hongying Zheng; Fei Yan; Yuwen Lu; Liying Sun; Lin Lin; Li Cai; Mingsheng Hou; Jianping Chen (Virus Genes, 2011)

Experimental investigation of the immunoregulatory and anti-inflammatory effects of the traditional Chinese medicine “Li-Yan Zhi-Ke Granule” for relieving chronic pharyngitis in rats - Yiyi Sun; Zhihe Zang; Xiaohong Xu; Zhonglin Zhang; Ling Zhong; Wang Zan; Yan Zhao; Lin Sun (Molecular Biology Reports, 2011)

Effects of plant growth regulators and l-glutamic acid on shoot organogenesis in the halophyte Leymus chinensis (Trin.) - Yan-Lin Sun; Soon-Kwan Hong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Study on the quantitative structure–toxicity relationships of benzoic acid derivatives in rats via oral LD50 - Ye-zhi Sun; Zuo-jing Li; Xin-li Yan; Lin Wang; Fan-hao Meng (Medicinal Chemistry Research, 2009)

Gadd45-α and Gadd45-γ utilize p38 and JNK signaling pathways to induce cell cycle G2/M arrest in Hep-G2 hepatoma cells - Na Zhu; Yan Shao; Lin Xu; Long Yu; LuHong Sun (Molecular Biology Reports, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Early Cretaceous gabbroic complex from Yinan, Shandong Province: petrogenesis and mantle domains beneath the North China Craton - Yi-Gang Xu; Jin-Long Ma; Xiao-Long Huang; Yoshiyuki Iizuka; Sun-Lin Chung; Yan-Bin Wang; Xiang-Yang Wu (International Journal of Earth Sciences, 2004)

Estradiol, aromatase and steroid receptors involved in the sex change of protandrous black porgy, Acanthopagrus schlegeli - Jin-Lien Du; Bih-Yun Lin; Yan-Hoarn Lee; Wen-Shiun Yueh; Chun-Lin He; Mong-Fong Lee; Lian-Tien Sun; Ching-Fong Chang (Fish Physiology and Biochemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)